Foam-enhanced compositions containing polyether-polysiloxane block copolymers, uses thereof, and methods of manufacture

By combining polyether-polysiloxane block copolymers with diol ether compounds and low-valent potassium salts with specific structures, the problems of insufficient foam retention and production stability of (AB)n type polyether modified organosilicon foam stabilizers in polyurethane foams have been solved, achieving high-performance and low-cost foam preparation.

CN117580913BActive Publication Date: 2026-11-06DOW TORAY CO LTD
View PDF 42 Cites 0 Cited by

Patent Information

Application Number
CN202280046144.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-06-04
Filing Date
2022-05-31
Publication Date
2026-11-06
Estimated Expiration
2042-05-31

AI Technical Summary

Technical Problem

In the existing technology, (AB)n type polyether modified silicone foam stabilizer has problems such as insufficient foam retention capacity, high production cost, susceptibility to batch differences of raw materials, and unstable viscosity in polyurethane foam manufacturing, making it difficult to widely use.

Method used

A composition is prepared by using a combination of polyether-polysiloxane block copolymers with a specific structure, a specific glycol ether compound, and a low-valent potassium salt via a hydrosilylation reaction. The composition ratio and potassium cation content are controlled to optimize the surface activity and foam retention capacity of the composition.

Benefits of technology

It is a high-performance foaming agent that achieves low cost and stable production. It has excellent foam holding power, bubble control and bubble stability. It is suitable for various polyurethane foams, especially exhibiting excellent microcell formation and foam holding power in microporous foams.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure QLYQS_3
    Figure QLYQS_3
Patent Text Reader

Abstract

The present invention provides a composition / foaming agent which has sufficient quality and foaming property even when a low-priced glycol ether compound is used as a raw material, and further has excellent foam enhancement performance. A composition and a method for producing the same, the composition containing a specific polyether-polysiloxane block copolymer (A') and a specific glycol ether compound (B') in a range of mass ratio (A'): (B') = 20-60:80-40 (here, the total amount of (A')(B') is set to 100), and further containing (K) a specific monovalent potassium salt in a range of 3-300 wt. ppm in terms of potassium atoms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a composition containing a polyether-polysiloxane block copolymer with a specific structure and a glycol ether compound, which improves foam reinforcement, and a method for manufacturing the same. Additionally, this invention relates to a surfactant containing the composition.

[0002] Polyurethane foam control agents (including functions as bubble control agents and bubble stabilizers, hereinafter referred to as...)

[0003] same). Background Technology

[0004] Through (1) organopolysiloxanes containing SiH groups at both ends and (2) organopolysiloxanes containing C=C groups at both ends

[0005] Linear organopolysiloxane-polyether block copolymers obtained by the hydrogenation and silanization of polyethers are known as non-hydrolyzable (AB)n type polyether modified organosilicones (Patent Documents 1, 2).

[0006] These block copolymers are obtained by hydrosilylation in toluene solvent, but toluene is derived from...

[0007] Due to its high risk of toxicity or flammability, it is typically removed from the product system by stripping under heating or reduced pressure. Similarly, xylene solutions containing this block copolymer are...

[0008] Known and commercially available, but also containing flammable and hazardous organic solvents.

[0009] question.

[0010] Patent document 3 discloses that after synthesizing the copolymer in toluene, it is added as a diluent.

[0011] The solvent exchange method is used to further remove toluene from the polypropylene glycol of the agent through a stripping operation.

[0012] For example, it was also mentioned that it can be used as a diluent in polyurethane foam formulations.

[0013] Polyols. Furthermore, as a comparative example, long-chain alkylbenzenes were proposed as the reaction solvent.

[0014] Commercially available foaming agents that also function as diluents. The solvent exchange method reduces the viscosity of (AB)n-type polyether-modified silicone.

[0015] In addition to improving the viscosity of the foaming agent to enhance workability, the low VOC (volatile organic compound) content of polyurethane foam is also important.

[0016] Organic Compounds (volatile organic compounds) are also advantageous in this respect, but there are...

[0017] Low production efficiency is caused by foaming during solvent exchange. Long-chain alkylbenzenes can simplify this process.

[0018] While the manufacturing process of the foaming agent has advantages, it also has the potential to leave residues in the polyurethane foam that become sources of VOCs.

[0019] This leads to the problem of migration (leaking) from the final product.

[0020] Patent document 4 relates to a method for manufacturing siloxane-polyoxyethylene copolymers by hydrogenation silanization under reduced pressure, disclosing an (AB)n type polyether modified silicone composition using IPP (isopropyl palmitate) as a reaction solvent and diluent. However, ester oils, represented by IPP, have the problem of easily separating, especially at low temperatures, due to poor compatibility with the copolymer. In addition, when included in a foaming agent, they may become a cause of VOCs and migration from polyurethane foam.

[0021] Patent document 5 discloses a technique for stably manufacturing non-hydrolyzable (AB)n type polyether-modified silicone or similar structures, particularly high molecular weight copolymers, without causing thickening or gelation. It illustrates an example where, after synthesizing the copolymer in flowing isoparaffins, unreacted low-boiling substances such as precipitates are removed by stripping (wherein a large portion of the flowing isoparaffins remains as a diluent for the copolymer). However, when flowing isoparaffins are included in the foaming agent, they can become a source of VOCs and migration from the polyurethane foam.

[0022] Patent Document 6 is an invention made to solve the problems addressed in Documents 1-5, disclosing a composition, a method for manufacturing the same, a foam stabilizer comprising the same, etc., said composition containing (A) a non-hydrolyzable (AB)n-type polyether modified organosilicon, and (B) a specific glycol ether compound in which the terminal hydrogen is replaced by a hydrocarbon group having 1 to 8 carbon atoms and having secondary alcoholic hydroxyl groups at other ends. This (B) component can be used as a reaction solvent and diluent for manufacturing the (A) component, and further, during the formation of polyurethane foam, it is introduced into the polyurethane resin backbone through the reactivity of the hydroxyl groups, thus having the advantage of simultaneously achieving VOC minimization of the foam and efficient production of the foam stabilizer.

[0023] In Patent Document 7, in response to the problem that the hydrosilylation of compounds containing SiH and compounds with olefinic unsaturated groups at the ends based on chloroplatinic acid catalysts cannot proceed sufficiently due to the occurrence of considerable side reactions in the presence of water or alcohols, a solution is proposed to carry out the hydrosilylation by coexisting with an aqueous buffer solution that maintains the pH of the system at 5 to 7 even in the presence of strong acids.

[0024] Patent document 8 discloses a process for preparing a general side-chain polyether-modified organosilicon surfactant via a hydrosilylation reaction in a high-boiling-point polyol solvent such as dipropylene glycol that does not have olefinic unsaturated groups, and a mixture consisting of the organosilicon surfactant and the polyol solvent (here, the polyol content in the mixture is at least 5 wt.%, and it contains at least 100 ppm of an alkali metal or alkaline earth metal salt of a C2-C19 monovalent carboxylic acid as a reaction promoter). In experimental example 9 of this document, an ethanolic solution of chloroplatinic acid was used as a catalyst for hydrosilylation, and potassium acetate was used as a buffer at 550 ppm relative to the total mixture.

[0025] Patent Document 9 describes a surfactant composition for flexible polyurethane foam comprising 99.98–90 wt.% of a non-hydrolyzable side-chain polyether-modified silicone suitable for the same purpose and 0.02–10 wt.% of an organic acid salt. In this technique, the addition of the organic acid salt and the manufacturing process of the polyether-modified silicone are independent of each other. The organic acid salt is added to the polyether-modified silicone either as a solid or as an aqueous solution, and heating to reduce the water content is optional. The resulting surfactant composition improves the height and permeability of the flexible polyurethane foam. In Additive No. 20 of the examples, a mixture of side-chain polyether-modified silicone, potassium oleate, and water in a ratio of 99.0:0.4:0.6 (mass ratio) was tested.

[0026] Patent Document 10 claims a method for manufacturing a general side-chain polyether-modified organosilicon based on hydrosilylation using a platinum catalyst in an organic solvent. The method is characterized by obtaining a low-odor polyether-modified organosilicon through the use of a high-purity monoalkenyl-terminated polyether with suppressed peroxide value and total carbonyl content. The method includes a post-reaction water distillation step, the addition of a predetermined amount of antioxidant, and optionally, the addition of a buffer that provides a pH of 5.5 to 8 when dissolved in water. In this technique, the buffer is added after the synthesis of the polyether-modified organosilicon. In Reference Examples 1-4, an IPA solution of chloroplatinic acid was used as the catalyst, and a methanol solution of sodium acetate (100 wt. ppm, based on sodium acetate, relative to the polyether-modified organosilicon composition excluding the organic solvent) was used as the buffer.

[0027] Patent Document 11 discloses a polyorganosiloxane-polyoxyethylene block copolymer [a specific (AB)n type polyether modified organosilicon], its preparation method, and a vesicle composition containing the same. In Examples 1-4, a dimethylsiloxane solution of a 1,3-diethyl-1,1,3,3-tetramethyldisiloxane platinum complex was used as a catalyst, and the reaction was carried out in xylene solvent in the presence of sodium acetate at 484-688 ppm to prepare the (AB)n type polyether modified organosilicon. In Examples 8-11, the same (AB)n type polyether modified organosilicon was prepared by using the same catalyst and reacting in IPA solvent in the presence of sodium acetate at 438-500 ppm. These reaction solvents were removed by stripping after the reaction.

[0028] It should be noted that Patent Document 11 discloses a variety of reaction solvents that can be used as needed in the manufacture of the (AB)n type polyether modified organosilicon, including monoethers of propylene glycol or dipropylene glycol, but this is only disclosed as a non-limiting example of an optional solvent. Furthermore, among these various solvents, several are listed as impractical for manufacturing (AB)n type polyether modified organosilicon due to their potential to hinder the reaction, cause inhomogeneity of the reaction system, or lead to side reactions. To explore the optimal solvent, those skilled in the art would need to conduct extensive experiments to verify the reactivity and stability of these solvents, and there is a lack of specific description regarding the selection of suitable solvents. In particular, no description or suggestion is made regarding the fact that specific glycol ether compounds with (B) terminal hydrogen replaced by hydrocarbon groups having 1 to 8 carbon atoms and secondary alcoholic hydroxyl groups at other terminals can be used as a reaction solvent and diluent for the synthesis of (AB)n-type polyether-modified organosilicones with a structure suitable as the main component of a foaming agent for polyurethane foams; improvements to the industrial production process of such foaming agents based on this; and the realization or benefit of microcellularization of polyurethane foams based on the good compatibility of such foaming agents with premixed liquids. Therefore, Patent Document 11 does not provide explicit teachings that would be understandable to a person skilled in the art regarding the invention and technical benefits of Patent Document 6.

[0029] Patent document 12 discloses a manufacturing process for polyether-modified organosilicon with a -SiOC- content of less than 1 mol%. This process comprises a hydrosilylation reaction of a polyether having at least one terminal unsaturated aliphatic hydrocarbon group and an alkali metal content of less than 50 ppm with an organohydrosiloxane having an acid value of less than 0.005. In experimental examples, the synthesis reaction of general side-chain polyether-modified organosilicon was carried out entirely under solvent-free conditions. It was reported that the addition of 13 ppm sodium acetate (Comparative Example 4) or 15 ppm potassium acetate (Comparative Example 5) to the reaction system resulted in a delay in the reaction rate. This technology is based on the concept that by using refined raw materials with low ionic impurity content on both the siloxane side and the polyether side involved in the hydrosilylation, excellent reactivity is continuously maintained in the reaction system without interruption, resulting in stable and efficient production of polyether-modified organosilicon. In addition, a variety of reaction solvents that can be used are disclosed, including monoethers of propylene glycol or dipropylene glycol, but no mention is made of the specific problems or causes that arise when these are used as synthetic solvents for (AB)n type polyether modified organosilicon.

[0030] Patent Document 13 discloses compositions containing general side-chain type polyether modified organosilicon and substances similar to (B), methods for their manufacture, and foam stabilizers containing them. Paragraph 0084 shows that buffers such as alkali metal salts of carboxylic acids can be added for purposes such as suppressing side reactions, and several options regarding methods of addition. Furthermore, it describes that when a polar solvent is used in the dissolution of this salt, removal based on a stripping operation can be carried out arbitrarily before or after the main reaction begins. However, the types and methods of using buffers are limited to non-limiting disclosures, and no buffers are used in the examples / comparative examples; there is no information whatsoever regarding the appropriate amount of buffer components to be added. Furthermore, it is difficult to discern from Patent Document 12 the specific problems arising when using the low-cost (B) raw material as a synthesis solvent for (AB)n type polyether modified organosilicon (A), and therefore no specific and particular means are shown regarding the optimal solution.

[0031] As mentioned above, in Patent Documents 1-13, various weakly basic buffers are considered to be used as additives in the manufacturing process of hydrosilane-modified polyether silicones. However, their function or expected effect is based on the function of buffers to neutralize acidic substances in the system (thereby inhibiting side reactions during manufacturing, promoting the main reaction, or inhibiting changes over time during product storage). That is, the weakly basic buffers in these documents, as expressed in words, include various buffers, reaction promoters, catalyst modifiers, additives for deodorization, etc., but their fundamental function is attributed to neutralization or pH adjustment of the system.

[0032] That is, in Patent Documents 1 to 13, there is no record or indication that the inventors discovered the following new function: in a composition containing "(AB)n type polyether modified organosilicon" and "a specific glycol ether compound in which the terminal hydrogen is replaced by a hydrocarbon group having 1 to 8 carbon atoms and has secondary alcoholic hydroxyl groups at other ends" as main components, when a specific potassium salt is present in the composition in a small amount in a soluble manner, the composition is endowed with a specifically enhanced surface activity / foam retention ability.

[0033] Furthermore, in patent documents 1-13,

[0034] When (A)(AB)n type polyether is modified into organosilicon

[0035] Synthetic reactions based on hydrosilylation

[0036] A specific glycol ether compound whose (B) terminal hydrogen is replaced by a hydrocarbon group having 1 to 8 carbon atoms and which has secondary alcoholic hydroxyl groups at other ends.

[0037] When the reaction solvent is used, the aforementioned problems with the quality of the foaming agent, which is based on the low-priced raw material (B) and whose main components are (A) or (A) and (B), are not documented or implied. The effect of a limited amount of a specific potassium salt on the quality and production stability of the foaming agent is not documented or implied.

[0038] Existing technical documents

[0039] Patent documents

[0040] Patent Document 1: US Patent No. 3,957,842 (Japanese Patent Application Publication No. 56-22395)

[0041] Patent Document 2: US Patent No. 4150048

[0042] Patent Document 3: Japanese Patent Application Publication No. 08-156143

[0043] Patent Document 4: US Patent No. 5,869,727 (Japanese Patent Application Publication No. 11-116,670)

[0044] Patent Document 5: Japanese Patent Application Publication No. 2006-282820 (Japanese Patent No. 4875314)

[0045] Patent Document 6: International Publication No. 2016 / 166979 (US Patent No. 10717872)

[0046] Patent Document 7: U.S. Patent No. 3,398,174

[0047] Patent Document 8: U.S. Patent No. 4,857,583 (Japanese Patent Application Publication No. 1-87633)

[0048] Patent Document 9: US Patent No. 5,472,987 (Japanese Patent No. 2,599,237)

[0049] Patent Document 10: US Patent No. 5,696,192 (Japanese Patent Application Publication No. 9-202829)

[0050] Patent Document 11: International Publication No. 2005 / 103117

[0051] Patent Document 12: US Patent No. 8008407 (Japanese Patent No. 5101598)

[0052] Patent Document 13: International Publication No. 2018 / 074257 (US20200048427A1) Summary of the Invention

[0053] The problem that the invention aims to solve

[0054] On the one hand, the inventors discovered new problems and solutions not documented in these patent documents during the development of this invention. In recent years, foam retention capacity has become a crucial requirement for foam stabilizers, particularly in the manufacture of microporous foams, where (AB)n-type polyether-modified silicone is the primary application. Specifically, even when designing low-density foams by reducing the amount of foam stabilizer added (cost reduction) and increasing the amount of blowing agent or entrained gas, it is easy to obtain foams with acceptable physical properties (achieving energy savings based on lightweighting). Therefore, there is a strong demand for foam stabilizers for microporous foams with strong foam retention capacity.

[0055] The conventional method for improving foam retention is to design a foam stabilizer formulation to obtain a high molecular weight / high viscosity product with a large n-number, i.e., to react the raw material polyether with a C=C / SiH molar ratio close to 1.0. However, in this method, it is known that small metering errors in the raw materials, batch-by-batch quality variations, or differences in manufacturing conditions can significantly affect the viscosity of the resulting foam stabilizer, leading to a high frequency of non-standard product manufacturing. Furthermore, the poor manufacturability or processability of high-viscosity products inevitably leads to further cost increases. Therefore, despite its excellent performance, (AB)n-type polyether-modified silicone is sometimes difficult to popularize in the market.

[0056] Here, the technology in Patent Document 6 provides some improvement to this complex and multifaceted problem, but there is room for further improvement in terms of industrial simplicity or production efficiency. In particular, foaming agents require inexpensive, industrially abundant, and stable supply, thus the foaming agent compositions obtained using existing technologies that require high levels of production management have unresolved issues in their marketability.

[0057] As described above, (AB)n type polyether-modified silicone can be used to design the average molecular weight of the copolymer, and its surface activity or affinity for polyurethane foam systems can be controlled by the EO / PO ratio or size of the polyether portion, the weight percentage of the silicone portion, etc. Therefore, it can perform excellently as a surfactant for bubble control or bubble stabilization in various polyurethane foam formulations. However, in the prior art, there are manufacturing problems, performance or quality problems directly related to the industrial production costs mentioned above, and insufficient market penetration due to these problems despite its potential value.

[0058] In view of the market demand for silicone foam stabilizers for polyurethane foams and the widespread availability of high-performance silicone foam stabilizers, there is a strong desire to develop foam stabilizers using (AB)n type polyether modified silicone, their manufacturing process, and formulations using them. These stabilizers should be low in cost, not easily affected by slight errors in raw materials or batch variations (acid value, etc.), stable and easy to manufacture, cost-effective and readily available, and possess sufficient performance for applications in polyurethane foams, particularly in foaming properties, bubble reinforcement, bubble control, and bubble stability within the foam system.

[0059] Solution for solving the problem

[0060] To address the aforementioned problems, the inventors conducted in-depth research and discovered that by comprising (A') a polyether-polysiloxane block copolymer with a specific structure, (B') a specific glycol ether compound, and (K) a potassium salt consisting only of carbon, hydrogen, and oxygen, with 1 to 8 carbon atoms and having a monovalent counterion without a benzene ring structure, the mass ratio of component (A') to component (B') is in the range of 20:80 to 60:40, and the potassium cation (K) in component (K) is present in the range of 3 to 300 wt.ppm relative to the sum of components (A') and (B'). + The present invention is achieved by using the composition (hereinafter, sometimes referred to as "the composition") and its use to solve the above-mentioned problems.

[0061] More specifically, this composition comprises:

[0062] (A') has the following properties within the molecule: (1)

[0063] [Chemical Formula 1]

[0064]

[0065] (In the formula, R independently represents a monovalent hydrocarbon group with 1 to 9 carbon atoms that does not have an aliphatic unsaturated bond, a is a number from 1 to 200, x is a number from 2 to 4, and y represents the group formed by (C x H 2x O)y represents a polyether moiety with a molecular weight in the range of 400 to 5000, the polyether moiety contains at least one propylene oxide group, n is at least 2, and Y' represents a divalent hydrocarbon group with 2 to 8 carbon atoms bonded to adjacent silicon atoms via carbon-silicon bonds and to polyoxyethylene blocks via oxygen atoms.

[0066] The structural unit represented is a polyether-polysiloxane block copolymer;

[0067] (B') One or more glycol ether compounds, characterized in that the terminal hydrogen is replaced by a hydrocarbon group having 1 to 8 carbon atoms and has secondary alcoholic hydroxyl groups at other ends, the number of repeating olefinic units having 2 to 4 carbon atoms is in the range of 1 to 3, and it does not contain heteroatoms other than oxygen; and

[0068] (K) Potassium salts consisting only of carbon, hydrogen, and oxygen, with 1 to 8 carbon atoms, and possessing a monovalent counterion that does not contain a benzene ring structure.

[0069] Component (A'): The mass ratio of component (B') is in the range of 20:80 to 60:40, and it contains potassium cation (K) from component (K) in the range of 3 to 300 wt.ppm relative to the sum of component (A') and component (B'). + Furthermore, it can include

[0070] (S) as a solvent for component (K) is a liquid compound selected from (S1) water, (S2) a monovalent saturated alcohol having 1 to 4 carbon atoms, and (S3) a saturated diol compound having 3 to 9 carbon atoms; and / or

[0071] (C) A polyether compound that is compatible with the above-mentioned components (A'), (B') and (K) and is selected from specific components (C1) to (C3).

[0072] Similarly, the above problems are solved by surfactants, foam stabilizers for polyurethane foams, or premixes for polyurethane foams (hereinafter referred to as "surfactants, etc.") containing this composition.

[0073] Furthermore, the aforementioned problem is solved by a method for manufacturing this composition, which includes a step of pre-mixing a polyether containing alkenyl groups at both ends as a raw material for component (A') with component (K), and a step of obtaining component (A') by a hydrosilylation reaction in the presence of component (B'); or a step of obtaining component (A') by a hydrosilylation reaction in the presence of component (B'), and a step of adding component (K) after the hydrosilylation reaction. It should be noted that in any manufacturing method, a step selected from the filtration step, the addition and optional removal step of component (S), and the addition step of component (C) may be included.

[0074] Furthermore, the above-mentioned problems are solved by manufacturing methods including surfactants such as those described in the above-described manufacturing methods, polyurethane foam forming compositions including the present composition or the present composition obtained by the above-described manufacturing methods, and polyurethane foams using these as raw materials.

[0075] Invention Effects

[0076] According to the present invention, a (AB)n type polyether modified silicone composition and its manufacturing process can be provided. The (AB)n type polyether modified silicone composition is low in cost, not easily affected by slight errors in raw materials or batch variations, can be manufactured stably and easily, has excellent cost utilization and supply, and exhibits sufficient performance in applications as a foam stabilizer for polyurethane foams, particularly in foaming properties, bubble reinforcement, bubble control, and bubble stability within the foam system. Therefore, it is anticipated that surfactants and other foam stabilizers with high-performance (AB)n type polyether modified silicone as the main component can be widely adopted in the market, which is difficult in the prior art.

[0077] Furthermore, a surfactant comprising the composition and a method for manufacturing the same can be provided. Moreover, the composition (including the composition obtained by the above-described manufacturing method) is particularly useful as a foam stabilizer for polyurethane foams, exhibiting specifically enhanced surface activity / foam retention capabilities, thus enabling the provision of high-performance polyurethane foams with excellent industrial productivity using it as a raw material.

[0078] More specifically, according to the present invention, a polyether-polysiloxane block copolymer composition can be provided that excels in various fields such as high-density microporous foams based on mechanical foaming methods, other rigid foams, or flexible foams, particularly in terms of micropore formation and foam holding power, foaming power, and foam volume; it also exhibits excellent homogeneity or stability of the premix; and excellent compatibility with various components in foam-forming emulsion compositions. Furthermore, a foam stabilizer for polyurethane foams composed of this composition can be provided.

[0079] Furthermore, the composition of the present invention, by using the aforementioned component (K), exhibits excellent foam retention capabilities even in the (AB)n type polyether-modified silicone foam stabilizer, which has low viscosity or relatively low molecular weight. Therefore, it offers the following advantages: even without setting the C=C / SiH molar ratio close to 1.0 during manufacturing, practically adequate performance can be ensured, and production management becomes easier. Moreover, the manufacturing method of the present invention, which includes a hydrosilylation reaction, offers the following advantages: even when using raw materials with large batch variations or low-priced raw materials with slightly higher acid values ​​as the aforementioned component (B'), it is possible to stably and cost-effectively supply the market with (AB)n type polyether-modified silicone foam stabilizers possessing practically adequate performance and quality. Detailed Implementation

[0080] The following provides a detailed description of compositions comprising the polyether-polysiloxane block copolymers involved in this invention.

[0081] [Ingredient(A')]

[0082] Component (A') is one of the main components of this composition.

[0083] Within the molecule, it possesses the general formula (1):

[0084] [Chemical Formula 2]

[0085]

[0086] The structural unit represented is a polyether-polysiloxane block copolymer.

[0087] As long as the above structure is satisfied, there are no particular restrictions on the terminal groups of component (A'), but in the case of synthesis via the hydrosilylation reaction described later, the structure of its molecular chain end is preferably selected from...

[0088] Z 1 : Alkenyl, hydroxyl, alkoxy, or acetoxy groups that are partially bonded to the polyether; and

[0089] Z 2 Monovalent hydrocarbon groups, hydroxyl groups, alkoxy groups, C1-C8 alkylene oxide groups, or hydrogen groups bonded to silicon atoms and without heteroatoms.

[0090] One or more functional groups in it.

[0091] In the formula, R independently represents a monovalent hydrocarbon group with 1 to 9 carbon atoms that does not have an aliphatic unsaturated bond, exemplified by an alkyl group with 1 to 9 carbon atoms. Methyl is particularly preferred industrially. Y' is a divalent hydrocarbon group with 2 to 8 carbon atoms that is bonded to an adjacent silicon atom via a carbon-silicon bond and to a polyoxyethylene block via an oxygen atom, preferably a divalent hydrocarbon group with 3 to 4 carbon atoms, and particularly preferably isobutylene.

[0092] a is a number from 1 to 200, x is a number from 2 to 4, and y represents the result of (C) x H 2x O)y represents a polyether moiety with a molecular weight in the range of 400 to 5000, the polyether moiety containing at least one propylene oxide group, and n being a number of at least 2.

[0093] From the viewpoint of usability and operability as a foam stabilizer, it is particularly preferred that a is a number in the range of 10 to 45, y is a number in the range of 1500 to 5000 molecular weight of the polyether (polyoxyethylene) moiety, and the mass ratio of ethylene oxide (C2H4O) units constituting the polyether moiety is in the average range of 30% to 80%. Within the above range, the hydrophilicity of the polyether-polysiloxane block copolymer is well balanced, and it necessarily contains a certain amount of propylene oxide units or butene oxide units. Therefore, the compatibility of the polyol or isocyanate, which is the main component of the polyurethane foam forming composition, with the foam stabilizer is improved, which is beneficial for obtaining the desired foam stabilization effect based on the improved stability of the premix. The function as a surfactant or foam stabilizer, as well as the operability during or after synthesis, are also improved.

[0094] From the viewpoint of its usefulness as a foam stabilizer and the stability of the copolymer, the single or double ends of the polyether-polysiloxane block copolymer as component (A') are preferably capped with functional groups containing the polyether moiety. In this case, the terminal groups are preferably composed of Z. 1 The alkenyl, hydroxyl, alkoxy, or acetoxy group, which is represented and partially bonded to the polyether, is particularly preferably methylallyl. It should be noted that when an organopolysiloxane containing SiH groups at both ends is used as the raw material for component (A'), a portion of the terminal SiH group may sometimes react with the hydroxyl group of component (B') described later, and a portion of this terminal group may also become a residue from the glycol ether of (B').

[0095] On the other hand, the terminal groups of component (A') preferably do not contain reactive functional groups having heteroatoms, and particularly preferably do not contain reactive functional groups that are ring-opening reactive as epoxy groups or amine groups.

[0096] The average molecular weight of the copolymer can be designed by adjusting the molar ratio (reaction ratio) of the organopolysiloxane containing SiH groups at both ends and the polyether containing alkenyl groups at both ends, which is used as its raw material. Furthermore, surface activity and affinity for polyurethane foam systems can be easily controlled by adjusting the EO% or size of the polyether portion, or by introducing hydroxyl or hydrophobic groups into the copolymer ends. Therefore, this copolymer composition performs excellently as a surfactant for bubble control or bubble stabilization in various types of polyurethane foam formulations.

[0097] [Ingredient (B')]

[0098] Component (B') is one or more glycol ether compounds, characterized in that the terminal hydrogen is replaced by a hydrocarbon group having 1 to 8 carbon atoms and other terminals have secondary alcoholic hydroxyl groups, the number of repeating olefinic units having 2 to 4 carbon atoms is in the range of 1 to 3, and it does not contain heteroatoms other than oxygen. Component (B') is introduced into the composition as a solvent in the synthesis reaction of component (A'), and has the function of improving the workability of the composition, i.e., the foaming agent, or its compatibility with other components used in polyurethane foam formulations.

[0099] Component (B') is preferably a monohydric organic compound having a boiling point capable of distillation or distillation-based purification. Examples of such compounds include one or more glycol ethers selected from propylene glycol monobutyl ether, dipropylene glycol monobutyl ether, tripropylene glycol monobutyl ether, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, tripropylene glycol monomethyl ether, propylene glycol monopropyl ether, dipropylene glycol monopropyl ether, tripropylene glycol monopropyl ether, propylene glycol monoethyl ether, dipropylene glycol monoethyl ether, and tripropylene glycol monoethyl ether. Particularly preferred are one or more glycol ethers selected from dipropylene glycol monobutyl ether and tripropylene glycol monobutyl ether.

[0100] Here, the mass ratio of component (A') to component (B') is in the range of 20:80 to 60:40.

[0101] [Ingredient (K)]

[0102] Component (K) consists only of carbon, hydrogen, and oxygen, with the number of carbon atoms ranging from 1 to 8. It is a potassium salt having a monovalent counter anion without a benzene ring structure, and is a characteristic structure of the composition involved in this invention. Furthermore, components (A'), (B'), and (K) are used together, and the potassium cation (cation: K) in component (K) is... +When the amount of [a specific ingredient] is within a certain range, it can impart specifically enhanced surface activity / foam retention to the composition. Here, in order to achieve the technical effects of the present invention, the counter anion of component (K) cannot be a polyvalent anion with a valence of more than two valences or a counter anion with an alkyl or benzene ring (aromatic ring) structure having more than 9 carbon atoms. When using potassium salts containing these counter anions, it is sometimes impossible to achieve compatibility with other components or foam enhancement properties of the foam stabilizer.

[0103] Examples of such components (K) include potassium bicarbonate, potassium acetate, potassium propionate, potassium butyrate, potassium isobutyrate, and potassium 2-ethylhexanoate. Furthermore, the counter anion is particularly preferably composed of 1 to 4 carbon atoms. Potassium acetate or potassium bicarbonate are particularly preferred examples of components (K).

[0104] The amount of component (K) used is relative to the sum of components (A') and (B'), and includes potassium cations (K2) in component (K) in the range of 3 to 300 wt.ppm. + The amount of component (K) is more preferably in the range of 3 to 100 wt.ppm, and most preferably in the range of 3 to 50 wt.ppm. When the amount of component (K) used is within the range described above, the foam-enhancing properties of the composition and the foam stabilizer containing it are significantly improved compared to the use of components (A'), components (B'), or these used together in a specific mass ratio. On the other hand, the amount of component (K) used is critical; when it is outside the range described above, the technical effects such as foam enhancement cannot always be fully achieved.

[0105] Specifically, component (K) is a soluble potassium salt, thus exhibiting excellent compatibility with other components. However, when the amount is below the lower limit, it is sometimes too small to demonstrate foam-enhancing properties. When the amount exceeds the upper limit, it is detrimental to the effect in terms of cost. In addition, sometimes the component exceeds the limit of the compatibility balance of the formulation system and precipitates in the system, which instead exhibits defoaming or foam-suppressing effects.

[0106] When using alkali metal salts other than potassium salts, such as sodium salts, these salts have lower compatibility with other components compared to potassium salts, and therefore sometimes tend to precipitate in the system, exhibiting defoaming or foam-suppressing effects. [Technical and Industrial Significance of this Composition]

[0107] Because component (K) enhances the foam reinforcing properties of the foam stabilizer, this composition, compared to conventionally known (AB)n type polyether-modified silicone foam stabilizers, can achieve sufficient foam volume even with small amounts when used in polyurethane foams, which is advantageous from a cost perspective. Furthermore, even when used in foam designs (formulations) with increased blowing agent or entrained gas volume, this composition can homogenize / stabilize the foam compared to conventional foam stabilizers, thus ensuring that even low-density / lightweight foams can easily maintain strength.

[0108] This composition achieves effective foam reinforcement simply by including a specific amount of soluble potassium salt in the system. Compared to conventional methods that use co-surfactants and silicone foam stabilizers to achieve micropority, it offers the following advantages: it eliminates the need for prior research to optimize the compatibility, solubility, and foam reinforcement effects of co-surfactants, and it is simple to produce or introduce industrially. Therefore, it is expected to meet the needs of the polyurethane foam industry seeking energy conservation and low cost in commercial activities.

[0109] In addition, this composition improves the overall foaming performance caused by raw material quality variations, such as the viscosity or molecular weight of component (A'), batch deviations or acid value variations of component (B'). Therefore, it is expected to comprehensively solve the quality or manufacturing problems, and even application problems, that are difficult to overcome in the prior art and are directly related to the industrial production cost of polyether-polysiloxane block copolymer compositions, so as to make (AB)n type polyether modified silicone foaming agent widely available in the market and used as a high-performance raw material.

[0110] [Ingredients (S)]

[0111] Component (S), serving as a solvent for component (K), is one or more liquid compounds selected from (S1) water, (S2) monovalent saturated alcohols with 1 to 4 carbon atoms, and (S3) saturated diols with 3 to 9 carbon atoms. As (S3), from the viewpoint of compatibility with the formulation system, a saturated diol compound containing at least one secondary hydroxyl group in one molecule, whose chemical formula consists only of carbon, hydrogen, and oxygen, and whose carbon number is in the range of 3 to 9, is particularly preferred. By using component (S), the potassium salt containing the counter anion can be uniformly and easily added to the system. It should be noted that component (S) preferably exhibits excellent solubility, compatibility with other components, and safety as component (K), and may also be a mixture of two or more components selected from (S1) to (S3). Furthermore, component (S) may be partially or completely removed from the composition by known means such as stripping after component (K) has been added to the system.

[0112] (S1) is water, preferably water with few impurities such as ion-exchange water, pure water, ultrapure water, refined water, distilled water, and tap water.

[0113] Specific examples of (S2) include methanol, ethanol, n-propanol, isopropanol, n-butanol, and isobutanol. From the viewpoint of salt solubility, methanol or ethanol is preferred; from the viewpoint of safety, ethanol or isopropanol is preferred.

[0114] Specific examples of (S3) include propylene glycol, dipropylene glycol, tripropylene glycol, 1,3-butanediol, 1,2-pentanediol, 1,2-hexanediol, 2-methyl-2,4-pentanediol (hexanediol), 2-ethyl-1,3-hexanediol, glyceryl monohexyl ether, glyceryl monocyclohexyl ether, etc. From the viewpoint of salt solubility, propylene glycol, dipropylene glycol, 1,2-pentanediol, 1,2-hexanediol, and glyceryl mono(methyl-propyl) ether are preferred. From the viewpoint of compatibility with the composition, tripropylene glycol, 1,2-pentanediol, 1,2-hexanediol, 2-methyl-2,4-pentanediol, and glyceryl mono(butyl (C4) to hexyl (C6)) ether are preferred. These preferred (S3) compounds, when mixed with polyether polyols for polyurethane foams to form a premix, have the effect of improving the compatibility with the polyether polyol of component (A') and enhancing storage stability. When using saturated diol compounds containing two primary hydroxyl groups in one molecule, such as ethylene glycol, diethylene glycol, triethylene glycol, or polyethylene glycol as (S3), these compounds, when present in small amounts, can be transparently dissolved in the compositions involved in this invention. However, they are highly polar and inherently have poor affinity with the compositions of this invention, thus acting as cell openers during the formation of polyurethane foam. That is, this can become disadvantageous when microporous formation or increased foam cell volume is desired. However, it is optional to use these (S3) components in combination with the preferred (S3) components for the purpose of achieving a balance between foam properties such as air permeability and foaming phenomena.

[0115] In the process of manufacturing this composition, if component (S) is removed, component (S) is particularly preferably made using one or more solvents selected from water, methanol, and ethanol. On the other hand, if component (S) is not removed from this composition, one or more liquid compounds selected from propylene glycol, 1,2-pentanediol, and 1,2-hexanediol are particularly preferred.

[0116] The amount of component (S) used is preferably in the range of 20 to 15,000 wt.ppm relative to the sum of component (A') and component (B').

[0117] [Ingredient (C)]

[0118] Component (C) is a polyether compound that is compatible with components (A'), (B'), and (K) and is selected from components (C1) to (C3) below. It has the following advantages: by homogenizing the entire composition, the viscosity and other properties of the composition involved in this invention can be adjusted, improving ease of use and handling (operation) without adversely affecting the function of the composition as a foam stabilizer or surfactant. Furthermore, component (C) can be used, and is preferred, for adjusting the hydroxyl value in the polyurethane foam forming composition containing this composition, i.e., controlling various physical properties such as the crosslinking density or strength of the polyurethane foam. It should be noted that the timing of adding component (C) to the system can be arbitrarily chosen.

[0119] (C1) A polyether alcohol represented by the following general formula (2).

[0120] General formula (2):

[0121] [Chemical Formula 3]

[0122]

[0123] (In the formula, R represents a monovalent hydrocarbon group with 1 to 9 carbon atoms that does not have aliphatic unsaturated bonds, R" represents methyl or ethyl, k satisfies the condition 0≤k≤20, l satisfies the condition 4≤l≤50, and the wt.% of the ethylene oxide portion of the polyether portion is less than 60%)

[0124] As a preferred example of component (C1), polypropylene glycol n-butyl ether with k=0, R=n-C4H9, and R”=CH3 can be cited, which has the advantages of being easy to handle and readily available at low cost. In particular, polyether monools in the range of 4 ≤ l ≤ 33 have excellent compatibility with the composition and are preferred. Furthermore, when pursuing low VOCs or wanting to reduce the concentration of hydroxyl groups from (C1), polyether monools in the range of 10 ≤ l ≤ 33 are preferred.

[0125] (C2) Polyether diol represented by the following general formula (3).

[0126] General formula (3):

[0127] [Chemical Formula 4]

[0128]

[0129] (In the formula, R” means the same as above, k’ satisfies the condition 0≤k’≤10, l’ satisfies the condition 4≤l’≤70, and the wt.% of the ethylene oxide portion of the polyether portion is less than 30%)

[0130] As a preferred specific example of component (C2), polypropylene glycol with k' = 0 and R” = CH3 can be cited, which has the advantages of being easy to handle and readily available at low cost. In particular, polyether glycols in the range of 4 ≤ l' ≤ 34 have excellent compatibility with the composition and are preferred.

[0131] (C3) A polyether triol obtained by addition polymerization of an epoxide with 2 to 4 carbon atoms to glycerol and / or trimethylolpropane, wherein the wt.% of the ethylene oxide portion of the polyether part is less than 20 and the average molecular weight is in the range of 500 to 4500.

[0132] As a preferred example of component (C3), a polyether triol obtained by propylene oxide addition polymerization of glycerol is mentioned. Polyether triols with an average molecular weight of approximately 1500 to 3500 are easy to handle and have particularly excellent compatibility with the composition, and are therefore preferred.

[0133] Relative to the composition, component (C) may be contained in a range where the content of component (A') is 1% by mass or more.

[0134] [Antioxidants]

[0135] The polyether-polysiloxane block copolymer compositions involved in this invention can sometimes deteriorate due to gradual oxidation by oxygen in the air. To prevent this, antioxidants such as phenolic, hydroquinone, benzoquinone, aromatic amine, or vitamin-based antioxidants can be added to improve oxidative stability. Examples of such antioxidants include BHT (2,6-di-tert-butyl-p-cresol) and vitamin E.

[0136] The antioxidant is preferably contained in the range of 1 to 1000 wt.ppm, more preferably in the range of 50 to 500 ppm, relative to the sum of 100 parts by weight of the components (A'), (B'), and optional (C).

[0137] [Other optional ingredients]

[0138] This composition is preferably used primarily as a surfactant, and may also contain other polyether-modified silicones, linear silicones, or organic surfactants, without impairing its technical characteristics. In this case, the content of these surfactants is preferably not more than equal in mass to the total mass of the composition relative to the stated component (A'). It should be noted that such a composition can also preferably be used as a surfactant, particularly as a foaming agent for polyurethane foams.

[0139] In this composition, a buffering agent component different from component (K) may be added without impairing the technical effects of the invention and according to the manufacturing method described later. More specifically, potassium or sodium salts different from component (K) can be listed as buffering agents usable in the present invention, and this buffering agent is preferably prepared in the composition in the form of a buffering agent solution dissolved or dispersed in said component (S). By using a buffering agent, it is sometimes possible to suppress the rise in acid value of the composition, especially from component (B) and the hydrosilylation reaction catalyst, etc., thereby stabilizing the quality.

[0140] Examples of potassium or sodium salts that can serve as buffers include potassium carbonate, sodium carbonate, sodium bicarbonate, sodium acetate, sodium propionate, sodium butyrate, sodium isobutyrate, sodium 2-ethylhexanoate, sodium benzoate, potassium benzoate, sodium lactate, potassium lactate, sodium laurate, potassium laurate, sodium oleate, and potassium oleate, but these are not limited to. Furthermore, the chemical formula constituting the salt is composed only of carbon, hydrogen, and oxygen atoms, with a particularly preferred number of carbon atoms ranging from 1 to 4. Sodium acetate is the most preferred salt.

[0141] The amount of buffer and buffer solution used is relative to the actual amount of component (B') described later, which is in the range of less than 100 wt.ppm when converted to potassium or sodium.

[0142] In this composition, without impairing the technical effects of the invention, at least a portion of the components that can be used in the polyurethane foam forming composition described later may be added in advance as other optional components.

[0143] Organic solvents can be used in this composition, but the manufacturing method described later can avoid the use and mixing of aromatic hydrocarbon solvents such as BTX (benzene, toluene, xylene) solvents, thus meeting the current needs of the polyurethane industry that requires strict VOC / emission management or is free of BTX, etc.

[0144] [This composition]

[0145] This composition comprises the above-mentioned components (A'), (B'), and (K), as well as other optional components. The components can optionally be mixed and homogenized using component (C). Preferably, the overall viscosity of the composition at 25°C is in the range of 100–35,000 mm² / s. This composition is particularly preferably prepared in a manner that satisfies this viscosity range, or the content of components (C), (A'), and (B') can be adjusted according to the desired properties of the polyurethane foam.

[0146] [Use of this composition]

[0147] The polyether-polysiloxane block copolymer composition of this invention has organosilicon sites and polyether sites with different hydrophilicities within the molecule. Therefore, it can be used without particular limitation in the conventional uses of polyether-polysiloxane block copolymers, and can be used without particular limitation in surfactants, foam stabilizers, fiber lubricants or softeners, surface treatment or coating agents, reactive raw materials for other polymeric materials, etc. In particular, the polyether-polysiloxane block copolymer composition of this invention is useful as an industrial surfactant, and its formulation is not particularly limited to coatings, coating agents, building materials, hydrophilic agents, surface treatment agents, foaming resin compositions, etc. Furthermore, due to its function as a surfactant, it is particularly useful as an additive for coatings, emulsifier, solubilizer, and foam stabilizer for polyurethane foams.

[0148] Particularly preferred uses of this composition are as a surfactant, a foam stabilizer for polyurethane foam, or a premix for polyurethane foam. Its use as a foam stabilizer will be described in more detail below. It should be noted that in this specification, polyurethane foam is sometimes referred to as "polyurethane foam" or simply "foam."

[0149] [Use as a foaming agent]

[0150] As described above, the polyether-polysiloxane block copolymer composition involved in this invention has significantly improved foam reinforcement properties, can be manufactured relatively easily, is not easily affected by the quality of raw materials, and has excellent cost utilization. Therefore, it can be preferably used as a surfactant, especially a foam stabilizer, for bubble control or bubble stabilization when manufacturing foaming resins, especially polyurethane foams.

[0151] Especially when used as a foam stabilizer or premix for polyurethane foam, this composition has the following advantages: it is not limited to a simple bubble stabilizer; the control or design of the open cell ratio is easy; the homogeneity or stability of the premix is ​​excellent; in addition, it has excellent compatibility with various components in the emulsion composition for foam forming; and it also has excellent foam stabilization properties in microporous applications or low-resilience foam applications.

[0152] [Method for manufacturing this composition]

[0153] This composition can be manufactured by a step of hydrosilylating a polyether containing alkenyl groups at both ends of (a1) with an organopolysiloxane containing SiH groups at both ends of (a2) in the presence of component (B') to synthesize component (A'), and a step of adding component (K) before or after the hydrosilylating reaction. Further, it may optionally include a step selected from the filtration step of the resulting composition, a solvent removal step of component (K), and a step of adding component (C), and is preferred. The raw material components and each step are described in detail below.

[0154] [Raw Material Composition (a1)]

[0155] Component (a1) is derived from the following general formula (4):

[0156] [Chemical Formula 5]

[0157] YO(C x H 2x O) y -Y

[0158] (In the formula, x is a number from 2 to 4, and y represents the result of (C) x H 2x O)y represents the molecular weight of the polyether moiety, which is in the range of 400 to 5000. Y represents a monovalent hydrocarbon group with 2 to 8 carbon atoms at the end, which has a reactive C=C group. The polyether moiety contains at least one propylene oxide group.

[0159] The polyether represented by the polyether containing alkenyl groups at both ends is provided as a polyether-polysiloxane block copolymer (A') by a hydrosilylation reaction with the component (a2) described later.

[0160] Here, the group Y can be selected from vinyl, allyl, methyl allyl, isoprenyl, hexenyl, octenyl, etc., and is particularly preferred to be allyl and / or methyl allyl. y is preferably composed of (CxH2xO). y The molecular weight of the polyether portion is in the range of 1500 to 5000, and the mass ratio of ethylene oxide (C2H4O) units constituting the entire polyether portion is preferably in the range of 30% to 80% on average.

[0161] Generally, component (a1) is manufactured by nucleophilic substitution of a polyether with terminal hydroxyl groups and a strong base alkoxide with an alkenyl halide, followed by removal of low-boiling-point substances or byproduct salts. In this reaction, the hydroxyl group capping is often incomplete, typically containing a certain amount of impurity hydroxyl groups in group Y. The capping rate is preferably 90 mol% or more, more preferably 95 mol% or more, and particularly preferably 98 mol% or more.

[0162] The water content in component (a1) is preferably 0.5 wt.% or less, more preferably 0.2 wt.% or less, and particularly preferably 0.1 wt.% or less. Since component (a1) is hygroscopic, it may be dehydrated in the reactor before the hydrosilylation reaction begins, depending on the circumstances.

[0163] In addition, component (a1) is prone to oxidative degradation. Therefore, an antioxidant of approximately 100–1000 ppm can be added after the synthesis reaction of component (a1) is completed to dissolve it in the raw materials. A preferred antioxidant is vitamin E.

[0164] [Raw Material Composition (a2)]

[0165] Component (a2) is an organopolysiloxane represented by general formula (5) containing SiH groups at both ends.

[0166] General formula (5):

[0167] [Chemical Formula 6]

[0168]

[0169] (In the formula, R independently represents a monovalent hydrocarbon group with 1 to 9 carbon atoms that does not have an aliphatic unsaturated bond, and a represents a number from 1 to 200), the polyether-polysiloxane block copolymer (A') is provided by a hydrosilylation reaction with the component (a1).

[0170] Here, R is particularly preferred to be methyl. In addition, from the viewpoint of the usefulness and operability of the manufactured foaming agent, in the above general formula (5), a is preferably a number in the range of 10 to 45.

[0171] Component (a2) is typically manufactured by polymerizing an organosiloxane with SiH-terminated ends and a low-molecular-weight cyclic organosiloxane in a desired molar ratio in the presence of an acid catalyst. After reaching equilibrium, the catalyst is neutralized, and neutralizing salts are removed. In terms of the nature of the equilibrium reaction, the resulting system generally contains, in addition to the target organopolysiloxane with SiH-terminated ends, 10–15 wt.% of a low-molecular-weight cyclic organosiloxane.

[0172] Here, when using the polyether-polysiloxane block copolymer composition of the present invention as a foam stabilizer for low VOC / emission polyurethane foam, it is preferable that the composition does not substantially contain low molecular weight siloxanes with 20 or fewer silicon atoms.

[0173] On the other hand, in the manufacturing method of this composition, it is preferable that there is no stripping step after the synthesis of the copolymer (i.e., after the hydrosilylation reaction), which has the advantages of not easily causing foaming phenomena in the process and excellent production efficiency. Therefore, it is preferable to remove low molecular weight siloxanes, especially low molecular weight cyclic siloxanes, from component (a2) beforehand. There are many methods for removing low molecular weight siloxanes from component (a2). For example, there are methods that involve successively blowing small amounts of inert gases such as argon or nitrogen into the equilibrium mixture of organopolysiloxanes containing SiH groups while treating it under high temperature and high vacuum; methods that involve thinning the equilibrium mixture of organopolysiloxanes containing SiH groups into a thin film and stripping it under a reduced pressure of, for example, less than 0.5 mm and heating conditions of 50 to 130°C; and methods that involve adding an organic solvent that dissolves low molecular weight siloxanes but not high molecular weight siloxanes, such as methanol, ethanol, or acetone, to the equilibrium mixture of organopolysiloxanes containing SiH groups to extract and remove the low molecular weight siloxanes.

[0174] Specifically, in component (a2), the total content of low-molecular-weight cyclic siloxanes with 6 or fewer silicon atoms is preferably 3000 ppm (by weight) or less, and particularly preferably 300 ppm (by weight) or less. Examples of such low-molecular-weight cyclic siloxanes include, for instance, cyclic dimethylsiloxanes represented by the formula [(CH3)2SiO]n (where n is an integer from 3 to 10).

[0175] [Raw material components (K) and solvent components (S)]

[0176] Components (K) and (S), as already described, are the specified potassium salts and their solvents, and their use is as described above.

[0177] Component (K) can be added to the system alone, but it is preferred to add it as a solution pre-dissolved in component (S). By solubilizing component (K), it is possible to disperse it very uniformly and finely in the system compared to directly mixing it into the raw material system in a separate (solid particle) state. Furthermore, adding component (K) solubilized by component (S) is also advantageous in terms of the appearance (transparency) of the composition (product), and it also reduces the burden on filtration and purification processes.

[0178] The concentration of component (K) in component (S) can be designed based on the type of component (K) and its solubility in the selected component (S), and practically can be in the range of 0.5 to 20 wt.%, preferably 1 to 10 wt.%. It should be noted that when component (S) is water (S1), it is often a good solvent for potassium salt component (K), and depending on the type of salt, it can sometimes be dissolved at a concentration of 50 wt.% or higher. Such a high-concentration solution can also be used directly, but the amount added as a solution is relatively small, so the influence of measurement error needs to be considered. Furthermore, whether it can be quantitatively added to the raw material system without loss requires attention or countermeasures to prevent stagnation in the charging line. In addition, in the preparation of the mixture of components (S) and (K), a method can be adopted to first prepare a high-concentration aqueous solution using water (S1), and then dilute it by adding appropriate amounts of the aforementioned (S2) and / or (S3).

[0179] As described in the ingredient (S), in the manufacturing method of the present invention, when removing ingredient (S), it is particularly preferable to use one or more solvents selected from water, methanol, and ethanol. On the other hand, when not removing the ingredient (S), it is particularly preferable to use one or more solvents selected from propylene glycol, 1,2-pentanediol, and 1,2-hexanediol.

[0180] Component (K) is preferably present together with component (a1) in the form of a mixed solution containing component (S), or mixed in the composition after the hydrogenation silylation reaction. Here, the difference in the timing of adding component (K), preferably dissolving component (K) in a mixed solution of component (S), is closely related to the first and second manufacturing methods involved in this invention.

[0181] In the first manufacturing method, a uniform and fine dispersion of component (K) in the system is achieved by adding component (K) to component (a1) before the hydrosilylation reaction, preferably by dissolving component (K) in a mixed solution of component (S). Furthermore, by pre-dispersing component (K) in component (a1), it is advantageous to effectively neutralize acid impurities in the raw materials (especially acid impurities from the quality of component (B')). It should be noted that component (S) may optionally be removed from the raw material system before the start of the hydrosilylation reaction for the purpose of suppressing side reactions.

[0182] On the other hand, in the second manufacturing method, after the hydrosilylation reaction of components (a1) and (a2), a mixed solution of component (K), preferably component (K) dissolved in component (S), is added to the composition. Alternatively, adding component (K) midway through the hydrosilylation reaction is also optional.

[0183] [Raw Material Composition (B')]

[0184] Component (B') is the glycol ether compound used in the amount described above. In the manufacturing method of the present invention, component (B') functions as a solvent for component (A') and its raw material components in the hydrosilylation reaction, and is used as a solvent in the synthesis reaction, thus becoming component (B') in the composition of the present invention.

[0185] In the manufacturing method according to the present invention, when using a single glycol ether, it is desirable that its purity is at least 90 wt.%. The purity is preferably 95 wt.% or higher, and particularly preferably 98.5 wt.% or higher. When using multiple glycol ethers as raw material (iv), the purity of each glycol ether is also preferably high, as described above.

[0186] Furthermore, as mentioned above, component (B') may sometimes contain trace amounts of acidic substances due to factors such as the manufacturer or storage conditions. The content of acidic substances in component (B') is preferably 0.02 wt.% or less, more preferably 0.01 wt.% or less, and particularly preferably 0.001 wt.% or less.

[0187] The water content in component (B') is preferably 0.5 wt.% or less, more preferably 0.2 wt.% or less, and particularly preferably 0.1 wt.% or less. Component (B') is hygroscopic; therefore, depending on the circumstances, it may be dehydrated in the reactor before the start of the hydrosilylation reaction.

[0188] It should be noted that, in this invention, when a certain amount of component (K) is used, and the amounts of the synthesized components (A') and (B') meet the aforementioned range, it has the advantage of being able to reduce the influence of acidic substances and other factors on the quality of component (B').

[0189] [Raw material composition: Hydrosilylation reaction catalyst]

[0190] In the manufacturing method of this invention, the aforementioned components (a1) and (a2) are reacted by a hydrosilylation reaction to form component (A') in the presence of an effective amount of hydrosilylation reaction catalyst. Here, the hydrosilylation reaction catalyst is not limited to any specific catalyst, as long as it can promote the hydrosilylation reaction; it can be appropriately selected from known hydrosilylation reaction catalysts for use in this invention. Specific examples of hydrosilylation reaction catalysts include particulate platinum, chloroplatinic acid, alcohol-modified chloroplatinic acid, olefinic complexes of chloroplatinic acid, coordination compounds of chloroplatinic acid and vinylsiloxanes, platinum black, and other platinum-containing hydrosilylation reaction catalysts adsorbed on silica micropowder or carbon powder supports.

[0191] In the manufacturing method of the present invention, a neutral platinum complex catalyst is particularly preferred for the hydrosilylation reaction, and 1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum complex is particularly preferred. On the other hand, when using acidic hydrosilylation reaction catalysts such as chloroplatinic acid or alcohol-modified chloroplatinic acid, the use or increase of the buffer component described later is sometimes necessary.

[0192] The amount of hydrosilylation catalyst used is an effective amount and is not particularly limited. However, when the total mass of components (a1) and (a2) is set to 100% by mass, the amount of metal atoms (especially platinum group metal atoms) in the hydrosilylation catalyst is 0.1 to 200 ppm by mass, preferably in the range of 1 to 50 ppm. This is because when the content of the hydrosilylation catalyst is less than the lower limit, the copolymerization reaction based on the hydrosilylation reaction sometimes becomes insufficient; when it exceeds the upper limit, it is uneconomical and sometimes adversely affects the transparency, such as the coloring, of the resulting composition.

[0193] [Raw material composition: buffer and buffer solution]

[0194] In the manufacturing method according to the present invention, the aforementioned buffer or a buffer solution in which the buffer is dissolved or dispersed in the component (S) can be used. In particular, potassium and sodium salts, as buffers, are added to the raw material system containing the component (a1) in the form of a buffer solution using component (S). Similar to component (K), compared to the case where the alkali metal salt, as the buffer, is directly mixed into the raw material system in the form of solid particles, a very uniform fine dispersion can be achieved. It should be noted that the solvent of component (S) can optionally be removed from the raw material system before the start of hydrosilylation for the purpose of suppressing side reactions, but this has the advantage of effectively neutralizing acid impurities in the raw material system (especially acid impurities from component (B') or the hydrosilylation reaction catalyst, etc., in the necessary minimum amount through the prior fine dispersion of the salt component. It should be noted that after finely dispersing the buffer or the like in the raw material system, removing component (S) has the advantage of reducing side reactions during the hydrosilylation reaction. It should be noted that, without removing component (S), a buffer or a buffer solution containing component (S) can also be added to the composition after the hydrosilylation reaction.

[0195] When preparing a buffer solution using component (S), the concentration of the alkali metal salt used as the buffer can be designed based on its solubility in the component (S) used, and is practically in the range of 0.5 to 20 wt.%, preferably 1 to 10 wt.%. It should be noted that water (S1) is often a good solvent for the buffer, and depending on the type of salt used as the buffer, it can sometimes be dissolved at a concentration of 30 wt.% or higher. Such a high-concentration solution can also be used directly, but the amount added as a solution is relatively small, so the influence of measurement error should be considered. Furthermore, whether it can be quantitatively added to the raw material system without loss requires attention or countermeasures to prevent stagnation in the loading line. It should be noted that when preparing the buffer solution, a method can also be used to first prepare a high-concentration aqueous solution, and then dilute it by adding appropriate amounts of component (S2) and / or component (S3).

[0196] The following describes in detail a method for manufacturing the composition using the aforementioned raw materials. As described above, the manufacturing method of the present invention can employ either the first or second manufacturing method, depending on the timing of adding component (K), particularly preferably a mixed solution of component (K) dissolved in component (S) (hereinafter sometimes referred to as "component (K) etc."), to the manufacturing system. It should be noted that these two manufacturing methods can also be combined to add component (K), preferably a mixed solution of component (K) dissolved in component (S), to the manufacturing system in multiple stages, as included in embodiments of the manufacturing method of the present invention.

[0197] [First Manufacturing Method]

[0198] In the first manufacturing method, it is essential to premix the component (K) and the like with the component (a1) before the hydrosilylation reaction. It should be noted that, optionally, the first manufacturing method may include a step of removing the solvent used during addition after the mixing step of the component (K) and the like.

[0199] More specifically, the first method for manufacturing the composition comprising a polyether-polysiloxane block copolymer (A') according to the present invention has the following characteristics:

[0200] Process (I):

[0201] The process of mixing component (a1) and component (K); and

[0202] Process (II):

[0203] The mixture obtained in process (I)

[0204] The process of carrying out a hydrosilylation reaction with component (a2) in the presence of component (B') and an effective amount of a hydrosilylation reaction catalyst (wherein, the potassium cation (K) in component (K) is contained in the range of 3 to 300 wt.ppm relative to the sum of components (a1), (a2), and (B'). + The amount of component (B) is used in a range where the mass ratio of component (A1) to component (B') is in the range of 20:80 to 60:40.

[0205] As a necessary step, it may optionally occur after step (I).

[0206] The process of removing component (S), which is used as a solvent when component (K) is added, from the system by heating and / or reducing pressure.

[0207] [Second Manufacturing Method]

[0208] In the second manufacturing method, a step of subsequently mixing the component (K) and the like in the reactants after the hydrosilylation reaction is necessary. It should be noted that the second manufacturing method may optionally include a step of pre-mixing the buffer or buffer solution with the component (a1), and a step of removing the solvent used when adding the buffer after this mixing step.

[0209] More specifically, the second manufacturing method of the composition comprising a polyether-polysiloxane block copolymer (A') according to the present invention has the following characteristics:

[0210] Process (I'):

[0211] The process of carrying out a hydrosilylation reaction of components (a1) and (a2) in the presence of component (B') and an effective amount of a hydrosilylation catalyst.

[0212] (Among them, the amount used is in the range of 20:80 to 60:40, where the sum of component (a1) and component (a2) is used to the mass ratio of component (B').

[0213] Process (II'):

[0214] In the process of adding component (K) to the composition after the hydrosilylation reaction in step (I'), and mixing the two components, the potassium cation (K) in component (K) is present in the range of 3 to 300 wt.ppm relative to the sum of components (a1), (a2), and (B'). + (Amount used)

[0215] For essential procedures, optional.

[0216] Prior to the step (I'), there is a step of adding a buffer or buffer solution to a raw material system containing at least component (a1), mixing the two, and then removing component (S), which is used as a solvent when adding the buffer, from the system by heating and / or reducing pressure.

[0217] [Filtration Process]

[0218] In the manufacturing method of this composition, it is preferable to further include a filtration step of the obtained composition after step (II) or before and after step (II'). Here, the filters, filter media, and other means used for filtration may be appropriately selected according to the manufacturing scale, the type or degree of foreign matter, but from the viewpoint of reducing waste, ensuring operator safety, work efficiency, and ensuring the quality or performance of this composition in foaming agent applications, Zeta potential adsorption filters, bag filters, cartridge filters, etc., are preferred.

[0219] There are no particular limitations on the above filtration process, but the composition after the hydrogen silanization reaction can be filtered in such a way that the transmittance (580nm) is 90% or more, more preferably 95% or more.

[0220] [Other reaction conditions]

[0221] In the hydrosilylation reaction process involved in this invention, the amount of terminal alkenyl group (R-Vi) in component (a1) is preferably equal to or slightly excess of the amount of silicon-bonded hydrogen atoms (Si-H) in component (a2). More specifically, the molar ratio (R-Vi) expressed as [R-Vi] / [Si-H] is preferably 1.0 to 1.5, and particularly preferably in the range of 1.1 to 1.3.

[0222] As described in Patent Document 6 (International Publication No. 2016 / 166979), generally speaking, the suitability of the polyether-containing silicone as a foaming agent is related to the type of foaming resin, and when arranged in order from suitable for low molecular weight foams to suitable for high molecular weight foams,

[0223] It becomes a highly elastic foam < rigid foam < soft foam < microporous foam.

[0224] Furthermore, the structure of the polyether moiety also significantly influences the size of the foam. Therefore, when reducing air permeability by decreasing cell size, a polyether structure with a high EO content is chosen; when stabilizing / retaining bubbles, a polyether with a large molecular weight is chosen, thus expanding the processing range. To ensure suitability for a wide range of applications / formulations, methods such as using multiple polyethers with different molecular weights or structures in the raw materials to expand the molecular weight distribution of the polyether moiety can also be applied in the polyether-polysiloxane block copolymer composition and its manufacturing method according to this invention. Additionally, since polyols, as one of the main raw materials for polyurethane, have PPG structural units, from the viewpoint of compatibility in foam formulations, it is often desirable for the polyether moiety in polyether-modified silicone to also contain PO (propylene oxide) chains.

[0225] The requirements for the foam stabilizer vary depending on the type of polyurethane foam formulated with the (AB)n type polyether modified organosilicon composition involved in this invention. However, since the chain length of organopolysiloxane (a2) with SiH groups at both ends represented by the general formula (5), or the type of polyether (a1) with alkenyl groups at both ends represented by the general formula (4), the reaction ratio or mass ratio of these can be appropriately adjusted, or the surface activity or affinity with the polyurethane foam system can be controlled according to the EO / PO% or molecular weight of the polyether portion, the preferred foam stabilizer can be freely designed according to expectations.

[0226] The hydrosilylation reaction conditions involved in this invention can be arbitrarily selected, but can be obtained by adding a small amount of antioxidants such as tocopherol (vitamin E) and heating and stirring at room temperature to 200°C, preferably 50 to 100°C, under an inert gas atmosphere such as nitrogen. It should be noted that the antioxidant can also be added after the hydrosilylation reaction is complete. The reaction time can be selected according to the reaction scale, the amount of catalyst used, and the reaction temperature, generally ranging from several minutes to several hours. Furthermore, the reaction can be carried out under reduced pressure for purposes such as quality improvement; for example, the reaction conditions proposed in Patent Document 4 (Japanese Patent Application Publication No. 11-116670) can be used without particular limitation.

[0227] The endpoint of the hydrosilylation reaction can be confirmed by the disappearance of Si-H bond absorption based on infrared spectroscopy (IR) or by the cessation of hydrogen production through the alkaline decomposition gas generation method described below. It should be noted that the amount of hydrogen produced can also be determined by analyzing the silicon atoms bonded to hydrogen atoms (Si-H) in organopolysiloxanes containing SiH groups at both ends as reactants. A summary is provided below.

[0228] <Alkali decomposition gas generation method: A method in which a solution of the sample dissolved in toluene or IPA is reacted with a 28.5% by mass potassium hydroxide solution in an ethanol / water mixture at room temperature, and the generated hydrogen gas is collected in a collection tube and its volume is determined>

[0229] In the manufacturing method of this composition, it is preferable to exclude the stripping step after the step of synthesizing the polyether-polysiloxane block copolymer (A') via a hydrosilylation reaction. This is to avoid foaming during the manufacturing process after the synthesis of component (A'). It should be noted that, from the perspective of ease of use and operability, it is preferable that the composition with components (A') and (B') as the main components has a viscosity in the range of 100 to 60,000 mm² / s at 25°C.

[0230] [Addition of ingredient (C)]

[0231] In the manufacturing method of this composition, component (C) can be further added to the composition with component (A') and component (B') as the main components, such that the content of component (A') is 1% by mass or more, and then the mixture is homogenized. The addition of component (C) is preferably after step (II) or before or after step (II'), at which time the viscosity of the entire composition containing component (C) is preferably between 100 and 35,000 mm at 25°C. 2 The viscosity range can be adjusted by varying the content of components (C), (A'), and (B') to meet the desired properties of the polyurethane foam, thereby homogenizing the mixture. It should be noted that, as already explained, the technical intent of adding component (C) is not limited to adjusting viscosity, etc.

[0232] [Addition of other optional ingredients]

[0233] In the method for manufacturing this composition, other optional components already described, component (B'), and component (C) may be added, and the mixture may be homogenized. Furthermore, in the method for manufacturing this composition, without impairing the technical effects of the invention, at least a portion of the components usable in the polyurethane foam forming compositions described later may be added as other optional components to this composition, and the mixture may be homogenized. This provides the advantage of being able to adjust a homogeneous premix for polyurethane foam containing both a foam stabilizer component and desired components.

[0234] [Benefits of this manufacturing method]

[0235] The manufacturing method of this composition utilizes inexpensive raw materials with varying quality and is highly efficient. Even with copolymers designed for high molecular weight or strong foam control, foam control problems arising during the manufacturing process are not caused or can be easily eliminated. Therefore, it offers excellent productivity and comprehensively addresses both manufacturing and quality issues directly linked to industrial production costs. Thus, by using the polyether-polysiloxane block copolymer composition obtained through this manufacturing method, it is expected that foam stabilizers containing this composition will achieve widespread and stable market adoption and can be utilized as high-performance raw materials.

[0236] As described above, the polyether-polysiloxane block copolymer compositions of the present invention (comprising compositions obtained by the above-described manufacturing method) are particularly useful as foam stabilizers used in the manufacture of polyurethane foams, and can be used directly as surfactants or foam stabilizers for polyurethane foams. Alternatively, they can be formulated into premixed liquids for polyurethane foams for system use.

[0237] [Polyurethane foam forming compositions comprising this composition and polyurethane foams]

[0238] The types, properties, and applicable formulations of polyurethane foams and polyurethane foams involved in this invention are not limited as long as they contain the polyether-polysiloxane block copolymer composition of this invention (including the composition obtained by the above manufacturing method) or are used as at least a part of the raw materials.

[0239] Generally, polyurethane foams are classified into rigid polyurethane foams and flexible polyurethane foams. More specifically, they can be broadly categorized into flexible polyurethane foams, high-elasticity polyurethane foams, rigid polyurethane foams, and specialty foams. For details on these, please refer, for example, to Patent Document 6 (International Publication No. 2016 / 166979). The compositions and foam stabilizers involved in this invention are universal and can achieve excellent effects or industrial production benefits even when formulated into various polyurethane foam formulations.

[0240] Furthermore, as mentioned above, the compositions and foam stabilizers involved in this invention are readily free of BTX solvent, enabling inexpensive and large-scale production, and are therefore suitable for obtaining low-VOC / emission polyurethane foams. Additionally, they facilitate the manufacture of BTX-free foams or premixed liquid systems by foam manufacturers or foam formulation (system) designers. It should be noted that, in order to produce polyurethane foams with low VOC / emissions or low odor, it is preferable to add a non-volatile antioxidant to the polyol described later.

[0241] The polyether-polysiloxane block copolymer composition of the present invention (including the composition obtained by the above manufacturing method) is preferably used as a raw material in a polyurethane foam forming composition comprising the following components: (d) a foam stabilizer.

[0242] (a) Polyols;

[0243] (b) Polyisocyanates;

[0244] (c) Catalyst;

[0245] (d) foam stabilizers; and

[0246] (e) Optionally selected from the group consisting of foaming agents, blowing agents, diluents, chain extenders, crosslinking agents, water, non-aqueous foaming agents, fillers, reinforcing agents, pigments, dyes, colorants, flame retardants, antioxidants, anti-ozone agents, UV stabilizers, antistatic agents, bactericides, and antimicrobial agents, other than component (d).

[0247] Regarding the raw material composition and its amount used in the polyurethane foam forming composition other than the foaming agent mentioned above (d), raw materials known in the art can be selected, for example, the components described in Patent Document 6 (International Publication No. 2016 / 166979).

[0248] It should be noted that the composition involved in this invention can be used as a foam stabilizer suitable for most polyurethane foams. The formulation amount is such that, relative to 100 parts by weight of (a) polyol, the (A') polyether-polysiloxane block copolymer in the composition ranges from 0.1 to 10 parts by weight, preferably from 0.5 to 5 parts by weight, and more preferably from 1.0 to 3.0 parts by weight.

[0249] The polyurethane foam obtained using the "composition comprising polyether-polysiloxane block copolymer (A')" as described in this invention can be rigid foam, semi-rigid foam, flexible foam, low-resilience foam, HR foam, or microporous foam. For details regarding these and their manufacturing processes, please refer, for example, to Patent Document 6 (International Publication No. 2016 / 166979). These polyurethane foams can be obtained by replacing at least a portion or all of the foaming agent described in Patent Document 6 with the composition described in this invention. Furthermore, in the manufacturing methods of foam stabilizers or polyether-polysiloxane block copolymer compositions described in the examples / comparative examples of Patent Document 3 (Japanese Patent Application Publication No. 08-156143) or International Publication No. 2021 / 131378, by adding and utilizing the method obtained in this invention [for example, by adding an appropriate amount of component (K) of this invention before the reaction and then allowing it to react], it is possible to arbitrarily enhance the foam properties of various polyurethane foams or adjust the cell size.

[0250] Furthermore, individual methods for manufacturing polyurethane foam can be appropriately selected, but particularly in the detailed descriptions of the following patent publications or patent publications, especially the examples, the (AB)n type polyether modified silicone composition involved in this invention is preferably used to replace part or all of the silicone-based foam stabilizer or silicone surfactant, or silicone copolymer surfactant. It should be noted that these detailed descriptions or disclosures of examples include disclosures related to the manufacturing apparatus, and that the components can be further replaced by ordinary design modifications by those skilled in the art, and the manufacturing conditions can be appropriately changed according to variations in viscosity, etc.

[0251] • US Patent No. 7,825,205 (Japanese Patent No. 5,422,115)

[0252] Japanese Patent Application Publication No. 2014-210832

[0253] Japanese Patent Application Publication No. 07-090102

[0254] • Patent document 3 (Japanese Patent Application Publication No. 08-156143) and Japanese Patent Publication No. 57-014797

[0255] • Patent document 6 (International Publication No. 2016 / 166979)

[0256] Methods for manufacturing polyurethane foam as described in Japanese Patent Publication Nos. 2005-534770, 2005-534770, and 2010-535931;

[0257] The manufacturing process of open-cell polyurethane as described in Japanese Patent Publication No. 2010-539280

[0258] Sealing materials containing urethane foam as described in Japanese Patent Application Publication No. 2012-246397, Japanese Patent Application Publication No. 2009-265425, etc.

[0259] Manufacturing of polyurethane foam as described in Japanese Patent Application Publication No. 2012-082273, Japanese Patent Application Publication No. 2010-247532, Japanese Patent Application Publication No. 2010-195870, and Japanese Patent Application Publication No. 2002-137234, etc.

[0260] Manufacturing of viscoelastic polyurethane foam as described in Japanese Patent Publication Nos. 2010-500447, 2010-504391, 2010-538126, 2011-528726, and 2013-529702.

[0261] Furthermore, the (AB)n type polyether modified silicone composition involved in this invention has the function of a surfactant, and therefore can also be used for industrial applications known for (AB)n type polyether modified silicone other than polyurethane foam, such as fiber treatment agents, fabric softeners, coating additives, etc.

[0262] Example

[0263] The present invention will be further described in detail below through examples and comparative examples, but the present invention is not limited thereto. It should be noted that in the following compositional formulas, the Me3SiO group (or Me3Si group) is denoted as "M", the Me2SiO group as "D", and the MeHSiO group as "M". H The unit obtained by modifying the methyl group in M ​​and D with any substituent is denoted as M. R and D R Additionally, IPA represents isopropanol, MeOH represents methanol, BDPG represents dipropylene glycol monobutyl ether, PG represents propylene glycol, EO represents ethylene oxide or vinyl oxyethylene, and PO represents propylene oxide or propylene oxide. Furthermore, unless otherwise specified, "%" in the experimental examples refers to weight (wt)%.

[0264] <Reference Data 1>

[0265] One feature of the composition and manufacturing method of the present invention is that it mitigates the influence of the quality of the raw materials used, achieving practically sufficient performance. Table 1 shows the supplier-based quality differences of BDPG; the purity, moisture content, acid value, etc., of BDPG from Company H and Company L differ. Table 1: Quality Differences Between BDPG Suppliers

[0266] [Table 1]

[0267]

[0268] In the following experimental examples, as a raw material component of linear organopolysiloxane-polyether block copolymers, the following were used:

[0269] (a1-1) Based on the average composition CH2=C(CH3)CH2-O(C2H4O) 35 (C3H6O) 27-CH2-C(CH3)=CH2 represents dimethyl allyl polyether (unsaturation degree 0.67 meq / g, hydroxyl value 0.8 mg-KOH / g).

[0270] (a1-2) Based on the average composition CH2=C(CH3)CH2-O(C2H4O) 35 (C3H6O) 27 -CH2-C(CH3)=CH2 represents dimethyl allyl polyether (unsaturation degree 0.64 meq / g, hydroxyl value 2.1 mg-KOH / g).

[0271] (a1-3) Based on the average composition CH2=C(CH3)CH2-O(C2H4O) 35 (C3H6O) 27 -CH2-C(CH3)=CH2 represents dimethyl allyl polyether (unsaturation degree 0.60 meq / g, hydroxyl value 3.8 mg-KOH / g).

[0272] (a1-4) Based on the average composition CH2=C(CH3)CH2-O(C2H4O) 35 (C3H6O) 27 -CH2-C(CH3)=CH2 represents dimethyl allyl polyether (unsaturation degree 0.63 meq / g, hydroxyl value 0.7 mg-KOH / g).

[0273] *Note: (a2-1)~(a2-3) correspond to different batches of raw materials for dimethyl allyl polyether.

[0274] Using (a2-1) from the average composition formula M H D 20 M H Methylhydropolysiloxane

[0275] Catalyst for the hydrosilylation reaction: a ligand solution of a platinum complex of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane (Pt concentration 0.43 wt%).

[0276] Additionally, when using BDPG manufactured by Company H or Company L as component (B'), it is designated as "(B')BDPG (Company H)" or "(B')BDPG (Company L)". [Initial evaluation of foaming (bubble enhancement effect) in each experimental example]

[0277] In the following experimental examples, the surface activity (bubble enhancement effect) of each composition was evaluated using the following method. That is, after the reaction, a very small amount of nitrogen gas was bubbled into the liquid to displace the system, just as during the reaction. The system was left to stand overnight in this state, and the compositions in the flasks were observed the following day and one week later, and evaluated according to the following criteria. The results obtained in the experimental examples are shown in Tables 2–4.

[0278] “Excellent”: At the observation time the next day, a large number of bubbles were present on the entire liquid surface, and this condition was maintained for one week.

[0279] "Good": At the observation time on the second day, there were a large number of bubbles on the entire liquid surface, and about 1 / 3 of the bubbles remained after 1 week.

[0280] "Few": At the time of observation the following day, there were very few bubbles on the surface of the liquid.

[0281] [Light transmittance (T%) in each experimental example]

[0282] In the following experimental examples, the transmittance at a wavelength of 580 nm was measured using a spectrophotometer for the transparency (T%) of each obtained composition. The results are presented as T% in the table.

[0283] [Example 1-1]

[0284] A 500 mL reactor was loaded with 46.58 g of (a2-1) methylhydropolysiloxane, 103.43 g of (a1-1) dimethyl allyl polyether (containing 500 ppm of natural vitamin E), 150 g of (B') BDPG (L company), and 0.30 g of (K+S) 3% potassium acetate PG solution (60 wt. ppm relative to BDPG based on potassium acetate). The mixture was heated to 50 °C under nitrogen atmosphere with stirring. 0.07 mL of hydrosilylation catalyst was added, and the mixture was allowed to mature at 50–80 °C for 3 hours. The reaction was then largely completed.

[0285] Therefore, it is obtained that the ratio of 50:50 contains at least the following components:

[0286] [Chemical Formula 7]

[0287]

[0288] (Here, a = 20, x1 = 35, y1 = 27, n ≈ 6)

[0289] The structural unit represented is a light brown, transparent liquid polyether-polysiloxane block copolymer composition of linear organopolysiloxane-polyether block copolymers (A') and (B') BDPG, with a volume of 1505 mm² / s (25°C).

[0290] Since the molar ratio of C=C groups to Si-H groups in the raw materials is set to C=C / SiH = 1.20, it is assumed that the two ends of the copolymer are mainly polyether-terminated (the terminal functional groups are methyl allyl or hydroxyl groups bonded to the polyether). Additionally, some Si-H groups can undergo dehydrogenation condensation with water or alcohols in the system during the reaction; therefore, it is assumed that a portion of the copolymer ends contains SiOH or SiO-R. 1 (R 1 The structure consists of residues such as BDPG. It should be noted that, here, the polyether moiety is a random addition of ethylene oxide and propylene oxide.

[0291] [Examples 1-2]

[0292] Replace 0.30 g of PG solution containing 3 wt.% potassium acetate (K+S).

[0293] Using 0.02 g of a 50 wt.% potassium acetate aqueous solution (60 wt. ppm relative to BDPG based on potassium acetate), the experiment was conducted in the same manner as in Examples 1-1, yielding a pale yellowish-brown transparent liquid polyether-polysiloxane block copolymer composition "1370 mm² / s, (25°C)".

[0294] [Examples 1-3]

[0295] Replace 0.30 g of PG solution containing 3 wt.% potassium acetate (K+S).

[0296] Using 0.60 g of a PG solution containing 3 wt.% potassium acetate (120 wt. ppm relative to BDPG based on potassium acetate), the experiment was performed in the same manner as in Examples 1-1, yielding a pale yellowish-brown transparent liquid polyether-polysiloxane block copolymer composition “1529 mm² / s, (25°C)”.

[0297] [Examples 1-4]

[0298] Replace 0.30 g of PG solution containing 3 wt.% potassium acetate (K+S).

[0299] Using 0.03 g of a PG solution containing 30 wt.% potassium acetate (60 wt. ppm relative to BDPG based on potassium acetate), the experiment was performed in the same manner as in Examples 1-1, yielding a pale yellowish-brown transparent liquid polyether-polysiloxane block copolymer composition “1450 mm² / s, (25°C)”.

[0300] [Comparative Example 1]

[0301] A 1L reactor was loaded with 75.25g of (a2-1)methylhydropolysiloxane, 174.75g of (a1-2) dimethyl allyl polyether, 250g of (B') BDPG (H company), and 0.25g of natural vitamin E. The mixture was heated to 80–90°C under nitrogen atmosphere with stirring. 0.56g of an IPA solution (Pt concentration 0.41wt%) of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum complex was added, and the reaction was allowed to proceed for 2.5 hours. A small amount of the reaction mixture was then collected and confirmed by alkaline decomposition gas generation (using an ethanol / water solution of KOH to decompose residual Si-H groups, and calculating the reaction rate based on the volume of hydrogen produced). The reaction was confirmed to be complete. Thus, a product containing at least the average composition of the formula was obtained in a 50:50 ratio.

[0302] [Chemical Formula 8]

[0303]

[0304] (Here, a = 20, x1 = 35, y1 = 27, n ≈ 6)

[0305] The structural unit represented is a linear organopolysiloxane-polyether block copolymer and BDPG, a generally transparent liquid polyether-polysiloxane block copolymer composition "1680 mm² / s, (25°C)".

[0306] It should be noted that while the average composition is presented simply, the molar ratio of C=C groups to Si-H groups in the raw materials is set to C=C / SiH = 1.18. Therefore, the copolymer ends are polyether-terminated (i.e., the terminal functional groups are methyl allyl or hydroxyl groups bonded to the polyether). Furthermore, some Si-H groups can undergo dehydrogenation condensation with water or alcohols in the system during the reaction; therefore, it is considered that a portion of the copolymer ends contains SiOH or SiO-R. 1 (R 1 The structure consists of residues such as BDPG or IPA. It should be noted that, here, the polyether moiety is a random addition of ethylene oxide and propylene oxide.

[0307] [Comparative Example 2-1]

[0308] 45.81 g of (a2-1) methylhydropolysiloxane, 104.19 g of (a1-3) dimethyl allyl polyether (containing 500 ppm of natural vitamin E), and 150 g of (B') BDPG (L company) were charged into a 500 mL reactor. The mixture was heated to 60 °C under nitrogen atmosphere with stirring. 0.04 mL of hydrosilylation catalyst was added, and the reaction was carried out at 60–80 °C for 3 hours. A small amount of the reaction solution was then collected and confirmed by alkaline decomposition gas generation, indicating that the reaction was largely complete. This yielded a product containing at least the average composition of [a specific ingredient] in a 50:50 ratio.

[0309] [Chemical Formula 9]

[0310]

[0311] (Here, a = 20, x1 = 35, y1 = 27, n < 6)

[0312] The structural unit represented is a linear organopolysiloxane-polyether block copolymer and an opaque liquid polyether-polysiloxane block copolymer composition of BDPG, "931 mm² / s, (25°C)".

[0313] The molar ratio of C=C groups to Si-H groups in the raw materials was set to C=C / SiH = 1.10. Therefore, it was assumed that the copolymer's ends were primarily polyether-terminated (the terminal functional groups were methyl allyl or hydroxyl groups bonded to the polyether). However, due to its opaque appearance, it was believed that a significant amount of Si-H groups underwent dehydrogenation condensation with the hydroxyl groups of BDPG during the reaction, resulting in insufficient molecular weight growth of the copolymer and a large amount of unreacted polyether remaining. It should be noted that here, the polyether portion is a random addition of ethylene oxide and propylene oxide.

[0314] [Comparative Example 2-2]

[0315] A 500 mL reactor was charged with 45.81 g of (a2-1) methylhydropolysiloxane, 104.19 g of (a1-3) dimethyl allyl polyether (containing 500 ppm of natural vitamin E), 150 g of (B') BDPG (L company), and 0.009 g of sodium acetate solid. The mixture was heated to 56 °C under nitrogen atmosphere with stirring. 0.08 mL of hydrosilylation catalyst was added, and the reaction was carried out at 60–80 °C for 6 hours, after which the reaction was largely completed. This yielded a product containing at least the average composition of [a2-1] in a 50:50 ratio.

[0316] [Chemical Formula 10]

[0317]

[0318] (Here, a = 20, x1 = 35, y1 = 27, n ≈ 6)

[0319] The structural unit represented is a linear organopolysiloxane-polyether block copolymer and a semi-transparent liquid polyether-polysiloxane block copolymer composition of BDPG, "1528 mm² / s, (25°C)".

[0320] Since the molar ratio of C=C groups to Si-H groups in the raw materials is set to C=C / SiH = 1.10, it is assumed that the two ends of the copolymer are mainly polyether-terminated (i.e., the terminal functional groups are methyl allyl or hydroxyl groups bonded to the polyether). Additionally, some Si-H groups can undergo dehydrogenation condensation with water or alcohols in the system during the reaction; therefore, it is assumed that a portion of the copolymer ends contains SiOH or SiO-R. 1 (R 1 The structure consists of residues such as BDPG. It should be noted that, here, the polyether moiety is a random addition of ethylene oxide and propylene oxide.

[0321] [Reference Example 1]

[0322] 104.19 g of (a1-3) dimethyl allyl polyether (containing 500 ppm of natural vitamin E) and 0.15 g of a 5 wt.% sodium acetate MeOH solution were charged into a 500 mL reactor. The reactor was heated while stirring under nitrogen circulation. MeOH was removed from the system by stripping at 60–80 °C and 2 mmHg for 30 minutes. Pressure was restored, and 45.81 g of (a1-1) methylhydropolysiloxane and 150 g of (B') BDPG (L company) were added with stirring. 0.08 mL of hydrosilylation catalyst was further added, and the reaction was carried out at 60–80 °C for 5 hours, after which the reaction was largely completed. This yielded a product containing at least the average composition of [a1-3] in a 50:50 ratio.

[0323] [Chemical Formula 11]

[0324]

[0325] (Here, a = 20, x1 = 35, y1 = 27, n ≈ 6)

[0326] The structural unit represented is a linear organopolysiloxane-polyether block copolymer and BDPG, a generally transparent liquid polyether-polysiloxane block copolymer composition "1619 mm² / s, (25°C)".

[0327] Since the molar ratio of C=C groups to Si-H groups in the raw materials is set to C=C / SiH = 1.10, it is assumed that the two ends of the copolymer are mainly polyether-terminated (i.e., the terminal functional groups are methyl allyl or hydroxyl groups bonded to the polyether). Additionally, some Si-H groups can undergo dehydrogenation condensation with water or alcohols in the system during the reaction; therefore, it is assumed that a portion of the copolymer ends contains SiOH or SiO-R. 1 (R 1 The structure consists of residues such as BDPG. It should be noted that here, the polyether moiety is a random addition of ethylene oxide and propylene oxide. This is also true in the following reference examples 2 and 3.

[0328] [Reference Example 2]

[0329] 86.19 g of (a1-1) dimethyl allyl polyether (containing 500 ppm of natural vitamin E) and 0.12–0.13 g of a 5 wt.% sodium acetate MeOH solution were charged into a 500 mL reactor. The reactor was heated while stirring under nitrogen atmosphere. MeOH was removed from the system by stripping at 60–80 °C and 1–3 mmHg for 40 minutes. Pressure was restored, and 38.81 g of (a1-1) methylhydropolysiloxane and 125 g of (B') BDPG (L company) were added with stirring. 0.06 mL of hydrosilylation catalyst was further added, and the reaction was carried out at 60–90 °C for 6 hours, after which the reaction was largely completed. This yielded a product containing at least the average composition of [a1-1] in a 50:50 ratio.

[0330] [Chemical Formula 12]

[0331]

[0332] (Here, a = 20, x1 = 35, y1 = 27, n ≈ 6)

[0333] The structural unit is a linear organopolysiloxane-polyether block copolymer and BDPG, in a generally transparent liquid form, with a flow rate of 1714 mm² / s (25°C). The molar ratio of C=C groups to Si-H groups in the raw materials is set to C=C / SiH = 1.20.

[0334] Here, Reference Example 2 is a reproduction test of Reference Example 1 with changes to the batch conditions of dimethyl allyl polyether, but the total amount of the main raw material is set to 250g, which differs from the experiment with 300g in Reference Example 1. Furthermore, considering the differences in the methyl allyl end-capping rate (distinguished by the residual hydroxyl value) or unsaturation (standard of average molecular weight) due to batch variations in the manufacturing of dimethyl allyl polyether, the C=C / SiH molar ratio was changed from 1.10 in Reference Example 1 to 1.20 so that the viscosity of the copolymer composition falls within the target range. By operating these manufacturing conditions and using a buffer solution (5 wt.% MeOH solution of sodium acetate), relatively good reproducibility was achieved.

[0335] <Comparative Example 3-1>

[0336] Replace 0.30 g of PG solution containing 3 wt.% potassium acetate (K+S).

[0337] Using 0.03 g of a PG solution containing 3 wt.% potassium acetate (6 wt. ppm relative to BDPG based on potassium acetate), the experiment was conducted in the same manner as in Examples 1-1, yielding a pale yellowish-brown, generally transparent liquid polyether-polysiloxane block copolymer composition “150 1 mm² / s, (25°C)”.

[0338] <Comparative Example 3-2>

[0339] Replace 0.30 g of PG solution containing 3 wt.% potassium acetate (K+S).

[0340] Using 0.03 g of a PG solution containing 2.5 wt.% sodium acetate (50 wt. ppm relative to BDPG based on sodium acetate), the experiment was conducted in the same manner as in Examples 1-1, yielding a pale yellowish-brown, generally transparent liquid polyether-polysiloxane block copolymer composition “1639 mm² / s, (25°C)”.

[0341] [summary]

[0342] The compositions in Examples 1-1 to 1-4 used a certain amount of a specific soluble potassium salt (component (K)) and BDPG manufactured by L Company, which is relatively inexpensive and has a slightly higher acid value, as raw materials. Compared with Comparative Example 1, Reference Example 2, etc., the viscosity of the compositions was slightly lower, but it can be confirmed that the transparency (i.e., light transmittance T%) of the compositions is excellent compared with these experimental examples, and the foaming (i.e., the bubble enhancement effect caused by surface activity) is significantly superior. Generally speaking, regarding compositions containing a "specific polyether-polysiloxane block copolymer (A')" as the main component, it has been previously believed that when the molecular weight or degree of polymerization of component (A') (the viscosity of the composition) is not high, the foam holding capacity required by the foam stabilizer for mechanical foaming is insufficient. However, the compositions according to the present invention achieve good transparency and bubble enhancement effects even with a slightly lower viscosity by using component (K) etc. Therefore, according to the present invention, even without strict control over the limiting viscosity of the polyether-polysiloxane block copolymer or the completion of the reaction in the synthesis reaction, it is possible to achieve a composition with practically sufficient foam-fixing properties and transparency, and it is expected that high-performance and inexpensive silicone foam-fixing agents can be produced efficiently and easily.

[0343] The results are shown in Table 2.

[0344] [Table 2]

[0345]

[0346] *In cases other than potassium, it is denoted as "(Na)". The same applies below.

[0347] On the other hand, Comparative Example 1 does not contain a buffer or component (K), and roughly corresponds to Reference Example 1-1 in International Publication No. 2016 / 166979 (Patent Document 6). By using BDPG manufactured by H Company, which has a low acid value, high purity, and is expensive, a composition with a practical viscosity and appearance, including the molecular weight of the copolymer, can be obtained, but its light transmittance is worse than that of Examples 1-1 to 1-4. Furthermore, BDPG manufactured by H Company is expensive, making it difficult to supply this composition to the market at a low price and in a stable manner.

[0348] In contrast, in Comparative Example 2-1, which used BDPG manufactured by Company L, a relatively inexpensive raw material with a slightly higher acid value, only a low-viscosity and opaque composition was obtained. Similarly, in Comparative Example 2-2, referring to the manufacturing methods of the embodiments in Patent Documents 8 and 11, an attempt was made to add sodium acetate in solid form to the synthesis reaction system of the (AB)n type polyether modified organosilicon involved in this invention as a buffer, but only a semi-transparent composition was obtained.

[0349] Reference Examples 1 and 2, using a method for manufacturing a buffer (sodium salt) and BDPG manufactured by Company L (which is relatively inexpensive and has a slightly higher acid value), yielded compositions with practical viscosity and appearance. However, in the embodiments of this application, although the viscosity is slightly lower, the transparency is higher, resulting in significantly superior foam enhancement / foam retention properties due to surface-active capabilities compared to these reference examples. This is believed to be based on the effect of using specific potassium ions as a component (K).

[0350] On the other hand, in Comparative Example 3-1, where the amount of component (K) was insufficient, and in Comparative Example 3-2, where sodium acetate was used instead of potassium salt and the manufacturing conditions were otherwise consistent with the example, the resulting compositions all had poor transparency and could not achieve foam enhancement / foam retention.

[0351] [Refer to Example 3, Examples 2-1 to 2-8, Comparative Examples 4-1 to 4-5]

[0352] The following shows the results when using different soluble potassium salts, based on the type / composition of the raw materials shown in Reference Example 3. It should be noted that Examples 2-1 to 2-8 are experimental examples using the component (K) of this application, and the reaction process includes examples (2-2, 2-3) based on Example 2-1 and examples (2-4 to 2-8) based on Reference Example 3. Furthermore, the foaming evaluation criteria are the same as in Examples 1-1, etc., and the results are shown in Table 3. However, regarding Examples 2-5 to Comparative Examples 4-1, in the experiment, the sample needed to be transferred and cleaned before verifying foaming; therefore, the record for "foaming" in Table 3 was set to Nodata, and the foam retention test described later was performed.

[0353] [Reference Example 3]

[0354] A 500 mL reactor was charged with 0.12–0.13 g of a MeOH solution containing (a1-4) dimethyl allyl polyether (containing 500 ppm of natural vitamin E) and 5 wt.% sodium acetate. The reactor was heated while stirring under nitrogen atmosphere. MeOH was removed from the system by stripping at 60–80 °C and 7–8 mmHg for 30 minutes. Pressure was restored, and 38.31 g of (a2-1) methylhydropolysiloxane and 125 g of (B') BDPG (L company) were added with stirring. 0.06 mL of hydrosilylation catalyst was further added, and the reaction was carried out at 70–80 °C for 3 hours, confirming the completion of the reaction. This yielded a product containing at least the average composition of [a1-4] in a 50:50 ratio.

[0355] [Chemical Formula 13]

[0356]

[0357] (Here, a = 20, x1 = 35, y1 = 27, n ≈ 6)

[0358] The structural unit is a linear organopolysiloxane-polyether block copolymer and BDPG, in a generally transparent liquid form, with a flow rate of 1634 mm² / s (25°C). The molar ratio of C=C groups to Si-H groups in the raw materials is set to C=C / SiH = 1.15.

[0359] The total amount of the main raw material was set to 250g, the same as in Reference Examples 2 and 3. Considering the differences in the methyl allyl end-capping rate (determined by the residual hydroxyl value) or unsaturation (standard of average molecular weight) from batch variations in the polyether manufacturing, the C=C / SiH molar ratio was changed from 1.20 in Reference Example 2 to 1.15 in order to bring the viscosity of the copolymer composition into the target range. However, regarding the effect of the finely dispersed sodium acetate (25 wt. ppm of the overall reaction system, compared to 50 wt. ppm for BDPG) in the manufacturing process and formulation of Reference Example 2, it is believed that it can be well reproduced in Reference Example 3, based on the viscosity and appearance of the copolymer composition.

[0360] [Example 2-1]

[0361] In a 500 mL reactor, 38.30 g of (a2-1) methylhydropolysiloxane, 86.70 g of (a1-4) dimethyl allyl polyether (containing 500 ppm of natural vitamin E), 125 g of (B') BDPG (L company), and 0.25 g of a 3% potassium acetate PG solution (60 wt. ppm based on potassium acetate relative to BDPG) were added and heated to 50 °C under nitrogen atmosphere with stirring. 0.03 mL of hydrosilylation catalyst was added, and the mixture was aged at 50–80 °C for 3 hours until the reaction was complete. This yielded a product containing at least the average composition of [a specific ingredient] in a 50:50 ratio.

[0362] [Chemical Formula 14]

[0363]

[0364] (Here, a = 20, x1 = 35, y1 = 27, n < 6)

[0365] The structural unit represented is a linear organopolysiloxane-polyether block copolymer and BDPG, a pale yellow transparent liquid polyether-polysiloxane block copolymer composition "1377 mm2 / s, (25°C)".

[0366] Since the molar ratio of C=C groups to Si-H groups in the raw materials is set to C=C / SiH = 1.15, it is assumed that the ends of the copolymer are mainly polyether-terminated (i.e., the terminal functional groups are methyl allyl or hydroxyl groups bonded to the polyether). Furthermore, it is believed that some Si-H groups undergo dehydrogenation condensation with water or alcohols in the system during the reaction, and that a portion of the copolymer ends contains SiOH or SiO-R. 1 (R 1 The structure consists of residues such as BDPG. It should be noted that, here, the polyether moiety is a random addition of ethylene oxide and propylene oxide.

[0367] [Example 2-2]

[0368] Replace 0.30 g of PG solution with 3 wt.% potassium acetate.

[0369] Using 0.28 g of a PG solution containing 3 wt.% potassium propionate (68 wt. ppm relative to BDPG based on potassium propionate), the experiment was conducted in the same manner as in Example 2-1, yielding a pale yellow, transparent liquid polyether-polysiloxane block copolymer composition “1285 mm² / s, (25°C)”.

[0370] [Examples 2-3]

[0371] Replace 0.30 g of PG solution with 3 wt.% potassium acetate.

[0372] Using 0.15 g of a 5 wt.% potassium acetate MeOH solution (60 wt. ppm relative to BDPG based on potassium acetate), the experiment was conducted in the same manner as in Example 2-1, yielding a pale yellow, transparent liquid polyether-polysiloxane block copolymer composition "1513 mm² / s, (25°C)".

[0373] [Examples 2-4]

[0374] Replace 0.12–0.13 g of MeOH solution containing 5 wt.% sodium acetate.

[0375] Using 0.15 g of a 5 wt.% potassium acetate MeOH solution (60 wt. ppm relative to BDPG based on potassium acetate), the experiment was performed in the same manner as in Reference Example 3, yielding a pale yellow, transparent liquid polyether-polysiloxane block copolymer composition “1527 mm² / s, (25°C)”.

[0376] [Examples 2-5]

[0377] Replace 0.12–0.13 g of MeOH solution containing 5 wt.% sodium acetate.

[0378] Using 0.16 g of a 5 wt.% potassium propionate MeOH solution (68 wt. ppm relative to BDPG based on potassium propionate), the experiment was performed in the same manner as in Reference Example 3, yielding a pale yellowish-brown transparent liquid polyether-polysiloxane block copolymer composition "1515 mm² / s, (25°C)".

[0379] [Examples 2-6]

[0380] Replace 0.12–0.13 g of MeOH solution containing 5 wt.% sodium acetate.

[0381] Using 0.19 g of a 5 wt.% potassium isobutyrate MeOH solution (76 wt. ppm relative to BDPG based on potassium isobutyrate), the experiment was performed in approximately the same manner as in Reference Example 3. The amount of catalyst required was 0.09 mL. A pale yellowish-brown transparent liquid polyether-polysiloxane block copolymer composition “1474 mm² / s, (25°C)” was obtained.

[0382] [Examples 2-7]

[0383] Replace 0.12–0.13 g of MeOH solution containing 5 wt.% sodium acetate.

[0384] Using 0.28 g of a 5 wt.% potassium 2-ethylhexanoate MeOH solution (112 wt. ppm relative to BDPG based on potassium 2-ethylhexanoate), the experiment was performed in the same manner as in Reference Example 3, and a pale yellowish-brown transparent liquid polyether-polysiloxane block copolymer composition “1520 mm² / s, (25°C)” was obtained.

[0385] [Examples 2-8]

[0386] Replace 0.12–0.13 g of MeOH solution containing 5 wt.% sodium acetate.

[0387] The experiment was conducted in largely the same manner as in Reference Example 3, except that 0.15 g of a 5 wt.% potassium bicarbonate aqueous solution (62 wt. ppm relative to BDPG based on potassium bicarbonate) was used. The reaction was slow, and even with 0.12 mL of catalyst, the consumption rate of SiH groups remained at 99.3%. An orange-transparent liquid polyether-polysiloxane block copolymer composition was obtained with a viscosity of 357 mm² / s (25 °C). Despite its low viscosity, the composition exhibited excellent surface activity in the foam retention test described later.

[0388] [Comparative Example 4-1]

[0389] Replace 0.12–0.13 g of MeOH solution containing 5 wt.% sodium acetate.

[0390] Using 0.38 g of a 5 wt.% potassium laurate MeOH solution (152 wt. ppm relative to BDPG based on potassium laurate), the experiment was performed in the same manner as in Reference Example 3, yielding a pale yellowish-brown transparent liquid polyether-polysiloxane block copolymer composition "1407 mm² / s, (25°C)".

[0391] [Comparative Example 4-2]

[0392] Replace 0.12–0.13 g of MeOH solution containing 5 wt.% sodium acetate.

[0393] The experiment was conducted in largely the same manner as in Reference Example 3, except that 0.10 g of a 5 wt.% potassium carbonate aqueous solution (42 wt. ppm relative to BDPG based on potassium carbonate) was used. The amount of catalyst required was 0.09 mL. A brown, generally transparent liquid polyether-polysiloxane block copolymer composition was obtained with a flow rate of 1508 mm² / s (25°C).

[0394] [Comparative Example 4-3]

[0395] Replace 0.12–0.13 g of MeOH solution containing 5 wt.% sodium acetate.

[0396] Using 0.25 g of a 5 wt.% potassium benzoate aqueous solution (98 wt. ppm relative to BDPG based on potassium carbonate), the experiment was conducted in the same manner as in Reference Example 3, yielding a light brown, generally transparent liquid polyether-polysiloxane block copolymer composition “1625 mm² / s, (25°C)”.

[0397] [Comparative Example 4-4]

[0398] Replace 0.12–0.13 g of MeOH solution containing 5 wt.% sodium acetate.

[0399] Using 0.17 g of an aqueous solution of 5 wt.% tripotassium citrate monohydrate (66 wt. ppm relative to BDPG based on tripotassium citrate), the experiment was performed in the same manner as in Reference Example 3, yielding a brown, opaque liquid polyether-polysiloxane block copolymer composition "1062 mm² / s, (25°C)".

[0400] [Comparative Examples 4-5]

[0401] Replace 0.12–0.13 g of MeOH solution containing 5 wt.% sodium acetate.

[0402] The experiment was conducted in largely the same manner as in Reference Example 3, except that 0.20 g of a 5 wt.% potassium lactate aqueous solution (78 wt. ppm relative to BDPG based on potassium lactate) was used. The amount of catalyst required was 0.09 mL. A brown, semi-transparent liquid polyether-polysiloxane block copolymer composition was obtained, “1634 mm² / s, (25°C)”. After the reaction was complete, the foam on the liquid surface largely disappeared the following day.

[0403] [Table 3]

[0404]

[0405]

[0406] *In cases other than potassium, it is denoted as "(Na)". The same applies below.

[0407] [summary]

[0408] Various potassium salts with different formulations were studied, and in Examples 2-1 to 2-8, which used soluble potassium salts equivalent to component (K) of this application, compositions with excellent transparency were obtained. Based on the results of foaming during the experiment and the foam retention test described later, it can be confirmed that these compositions have excellent foam-enhancing properties as foam stabilizers. On the other hand, in Reference Example 3 and Comparative Examples 4-1 to 4-5, the transparency (transmittance) of the compositions was insufficient, and foam-enhancing properties could not be confirmed.

[0409] [Example 3 and Comparative Example 5]

[0410] In the following experiments, the batch numbers of the main raw materials (polyether, polysiloxane, BDPG) were kept the same as in Reference Example 3 or Examples 2-4. As a design to make the C=C / SiH molar ratio close to 1.0, compositions containing highly polymerized polyether-polysiloxane block copolymers (A') were prepared under different conditions: "without buffer" vs. "with component (K): potassium acetate". The results are shown in Table 4.

[0411] [Example 3]

[0412] 81.45 g of (a1-4) dimethyl allyl polyether (containing 500 ppm of natural vitamin E) and 0.15 g of a (K+S) 5 wt.% potassium acetate MeOH solution were charged into a 500 mL reactor. The reactor was heated while stirring under nitrogen circulation. MeOH was removed from the system by stripping at 55–70 °C and 3–4 mmHg for 1 hour. Pressure was restored, and 43.57 g of (a2-1) methylhydropolysiloxane and 125 g of (B') BDPG (L company) were added with stirring. 0.09 mL of hydrosilylation catalyst was further added, and the reaction was carried out at 40–80 °C for 5.5 hours, after which the reaction was largely completed. This yielded a product containing at least the average composition of [a1-4] in a 50:50 ratio.

[0413] [Chemical Formula 15]

[0414]

[0415] (Here, a = 20, x1 = 35, y1 = 27, n > 10)

[0416] The structural unit represented is a linear organopolysiloxane-polyether block copolymer and BDPG, a pale orange transparent viscous liquid polyether-polysiloxane block copolymer composition “29600cP, (25°C)”.

[0417] [Comparative Example 5]

[0418] 43.56 g of (a1-1)methylhydropolysiloxane, 81.45 g of (a2-4) dimethyl allyl polyether (containing 500 ppm of natural vitamin E), and 125 g of (B') BDPG (L company) were charged into a 500 mL reactor. The mixture was heated to 45 °C under nitrogen atmosphere with stirring. 0.06 mL of a ligand solution (Pt concentration 0.43 wt%) of a 1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum complex was added, and the reaction was carried out at 45–80 °C for 4.5 hours, after which the reaction was approximately complete. This yielded a product containing at least the average composition of [a1-1] in a 50:50 ratio.

[0419] [Chemical Formula 16]

[0420]

[0421] (Here, a = 20, x1 = 35, y1 = 27, n < 10)

[0422] The structural unit represented is a linear organopolysiloxane-polyether block copolymer and BDPG, a brown, generally transparent liquid polyether-polysiloxane block copolymer composition “7300cP, (25°C)”.

[0423] [Table 4]

[0424]

[0425]

[0426] [summary]

[0427] By setting the true value of the molar ratio of C=C to Si-H groups in the raw materials, C=C / SiH, to close to 1.0 (0.95 based on simple calculations of the analytical results of each raw material), even when using BDPG manufactured by L Company, which is relatively inexpensive and has a slightly higher acid value, as shown in Comparative Example 5 (without buffer), a high molecular weight / high viscosity (AB)n-type polyether modified silicone composition can be obtained. However, as shown in Example 3, by incorporating the (K) potassium acetate buffer of the present invention into the raw material system and initiating the synthesis reaction, compared with Comparative Example 5, it can be confirmed that a further high molecular weight / high viscosity (AB)n-type polyether modified silicone composition is obtained, and its foaming reinforcement properties are also excellent.

[0428] [GPC Analysis Results]

[0429] As representative compositions among those involved in this invention, the following four samples were subjected to GPC (detector: refractometer) analysis using chloroform eluent. The results are shown in Table 5.

[0430] [Table 5]

[0431]

[0432] According to the GPC analysis results, a copolymer with a molecular weight exceeding 30,000, which is the standard for performance as a bubble stabilizer for polyurethane microporous foam, was confirmed. The proportion of unreacted polyether material with methyl allyl groups at both ends was also low. However, when comparing Comparative Example 5, synthesized without component (K) or a buffer, with Example 3, the designed degree of polymerization was n>10, but the actual number-average molecular weight of the copolymer obtained in Comparative Example 5 was lower based on GPC, and a large amount of unreacted polyether material remained compared to Example 3.

[0433] [Further performance evaluation as a foaming agent]

[0434] The aforementioned evaluation based on "foaming" can clearly distinguish between samples of a composition that foam very well and those that foam almost no way, but it lacks precision in evaluating subtle differences between samples in between or between samples with similar performance. Therefore, a more detailed performance evaluation of the compositions involved in the examples is conducted by performing a "foam retention test" using a homogeneous dispersion mixer, as described later.

[0435] [Preparation of Examples 4-1 to 4-3 (Filters)]

[0436] Before the foam retention test, the filter samples of Reference Examples 1 to 3 were prepared according to the following steps in order to serve as an evaluation criterion or a criterion for the subsequent addition of component (K) described later.

[0437] <Reference Example 4-1: Filter from Reference Example 2>

[0438] 100 g of the polyether-polysiloxane block copolymer composition obtained in Reference Example 2 was filtered through a 90 mm diameter Zeta potentiometric adsorption filter, yielding 80.3 g of a slightly yellow, transparent, and uniform filtrate. As a result, the transmittance T% (580 nm) of the composition improved from 78% before filtration to 97% after filtration.

[0439] <Reference Example 4-2: Filter material from Reference Example 3>

[0440] 100.1 g of the polyether-polysiloxane block copolymer composition obtained in Reference Example 3 was filtered through a 90 mm diameter Zeta potentiometric adsorption filter, yielding 80.8 g of a slightly yellow, transparent filtrate. As a result, the transmittance T% (580 nm) of the composition improved from 79% before filtration to 97% after filtration.

[0441] <Reference Example 4-3: Mixed Solution of Filtered Samples from the Reference Example>

[0442] Reference Example 1 (180g), Reference Example 2 (66g), and Reference Example 3 (115g) were filtered through a Zeta potentiometric adsorption filter with a diameter of 90mm. Reference Example 4-1 (35g) and Reference Example 4-2 (47g) were further mixed in the resulting filtrate to obtain 423g of a composition containing a polyether-polysiloxane block copolymer as a slightly yellow transparent liquid.

[0443] [Foam Retention Capacity Test]

[0444] For multiple samples of the aforementioned reference examples, embodiments, and comparative examples, the foam-retaining ability as a surfactant was tested using a homogeneous dispersion mixer according to the following steps. It should be noted that, in order to increase the stirring force, the orientation of the disperser's saw blade was fixed opposite to the direction of rotation.

[0445] [step]

[0446] 1. Place 30g of foaming agent sample into a clean 200mL wide-mouth glass bottle and let it stand.

[0447] 2. Measure and record the liquid level of the sample. Draw a line along the meniscus with an oil-based magic pen, and treat the height of the upper end of the line as the initial height of the liquid level. Generally, the lower end of the line should be 18 mm from the bottom of the bottle, and the upper end of the stopper should be 20 mm from the bottom of the bottle.

[0448] 3. Immerse the saw blade of the homogenizer into the center of the liquid, setting the height slightly above the level so that the saw blade does not touch the bottom of the glass bottle.

[0449] 4. Secure the glass bottle containing the sample with clamps.

[0450] 5. Use a homogenizer to stir at 3000 rpm for 2 minutes.

[0451] 6. After stirring stops, move the saw blade to a position about 1 cm high without contacting the foaming liquid and fix it in place. Run it idle for a short time to remove the liquid adhering to the saw blade.

[0452] 7. Remove the glass bottle and mark the height (top) of the foam with an oil-based magic pen. Calculate the difference between this height and the initial height [cm]. The magnitude of this value determines the foam's holding power.

[0453] (Note) Steps 6 and 7 are performed within a short period of approximately 30 seconds. Observations after the experiment show that...

[0454] The height of the foam produced remains almost unchanged for at least 3 to 5 minutes.

[0455] Table 6 below summarizes the physical properties and foam retention test results of each composition. It should be noted that the potassium addition amounts in the table are relative to BDPG in wt.ppm. In the series of evaluations in Table 6, Reference Example 4-2 was used as the benchmark for foam retention performance.

[0456] [Table 6]: Relationship between sample contents and foam holding power, cushioning system, etc.

[0457] [Table 6]

[0458]

[0459]

[0460] *In cases other than potassium, it is denoted as "(Na)". The same applies below.

[0461] Note: The Na [ppm] in Example 4-1 is a quantitative value based on the "acid decomposition-ICPMS method".

[0462] Table 6 confirms that the components of this composition, including KHCO3 as component (K) and a potassium monovalent carboxylate with a low steric hindrance, exhibit good compatibility and excellent foam-enhancing effect. On the other hand, insufficient use of potassium salt (Comparative Example 3-1), or the use of potassium salts containing long-chain alkyl anions, aromatic ring anions, or polyvalent anions (Comparative Examples 4-1 to 5), fails to achieve adequate foam-enhancing effect. It should be noted that Reference Examples 4-1 and 4-2 are samples with practical foam-holding properties, obtained by filtration to remove insoluble salts from the composition system; however, the compositions described in the examples demonstrate superior foam retention / surface activity compared to these reference samples.

[0463] It should be noted that, as described above, the foam-enhancing effect involved in this invention is a combination of components (A') and (B') in a specific ratio, and is a specific and significant effect exhibited only when a specific potassium salt is used within a certain range of amounts. Therefore, it is believed that even if only a non-specific buffer is used in the hydrosilylation reaction of components (A'), etc., the same effect cannot be confirmed.

[0464] [Examples 4, 5, Comparative Example 6, Reference Example 5: Evaluation of Premixed Solutions]

[0465] 6.0 g of each sample from Reference Example 4-1, Examples 2-4, Example 3, and Comparative Example 5 were mixed with 24.0 g of polypropylene glycol (average molecular weight 425, abbreviated as PPG-425), a type of polyether polyol, to prepare a premixed solution. At this time, the concentration of the polyether-polysiloxane block copolymer (A') in the solution was 10 wt.%. These were subsequently designated as Reference Example 5, Example 4, Example 5, and Comparative Example 6.

[0466] According to the [Foam Retention Test] and [Procedure] described above, the foam retention properties of these premixed solutions were tested. PPG-425 (30g) without a foam stabilizer was tested together with a reference sample. The results are summarized in Table 7 below. The foam volume increase rate [%] in the table is calculated based on the data from Comparative Example 5 (set to zero).

[0467] [Table 7]: Foam retention power of premixed solutions

[0468] [Table 7]

[0469]

[0470] Comparative Example 6 was considered a premixed liquid that could achieve practical foam retention. However, in the premixed liquid of Example 4, which used component (K), it was confirmed that the composition had a low viscosity and achieved superior foaming or foam retention properties compared to Comparative Example 6 or Reference Example 5, even in the form of a premixed liquid, the foam enhancement effect based on dissolved potassium cations was fully realized. It should be noted that the premixed liquid (Example 5) containing specific dissolved potassium cations and high molecular weight (A') can achieve the maximum and superior foam retention performance.

[0471] [Examples 6-1 to 6-6: Post-addition of component (K)]

[0472] For 60g of the sample from Reference Example 4-3, a suitable amount (variable) of 5 wt.% potassium acetate in PG solution or 5 wt.% potassium bicarbonate in aqueous solution was mixed to prepare samples (Examples 6-1 to 6-6). Then, the foam retention properties of these foaming agent compositions were tested according to the [Foam Retention Test] and [Steps] described above, and the results are shown in Table 8. Here, Reference Example 4-3 itself is used as the reference standard. It should be noted that the subsequent addition of component (K) corresponds to the second manufacturing method involved in this invention.

[0473] [Table 8]: Foam retention capacity of foam stabilizer compositions with added specific potassium salts

[0474] [Table 8]

[0475]

[0476] Based on the results in Table 8, the foam-enhancing effect of increasing the foam holding power of the foam stabilizer composition by adding a specific potassium salt solution after synthesizing component (A') in the presence of component (B') was confirmed. However, this foam-enhancing effect is limited compared to that achieved by adding component (A') to the raw material system before the start of the synthesis reaction (= first manufacturing method). Additionally, the transparency of the composition decreased in some samples.

[0477] [Examples 7-9: Compositions containing component (C) and their compatibility evaluation]

[0478] In the following experiments, samples from Examples 2-3 (hereinafter referred to as "Ex Sample" or "Ex") were mixed with component (C) to evaluate compatibility. Component (C) exhibiting excellent compatibility with Sample Ex was considered suitable as a diluent or a base polyol for premixed polyurethane foams containing the compositions involved in this invention. It should be noted that, as another effect of these diluents, the hydroxyl value of the foam stabilizer can be adjusted, thereby controlling the effect on the pre-designed strength or crosslinking density of the polyurethane foam. Furthermore, it is also effective in controlling the air permeability or cell size of the foam.

[0479] Here, the positioning of Examples 7 to 9 is as follows.

[0480] Example 7: Compatibility evaluation test of Ex sample with polyether alcohol (C1)

[0481] Example 8: Compatibility evaluation test of Ex sample with polyether diol (C2)

[0482] Example 9: Compatibility evaluation test of Ex sample with polyether triol (C3)

[0483] [Compatibility Evaluation Test]

[0484] The Ex sample and component (C) were mixed in three stages at a total of 10g, with the Ex / C ratios being 5.0g / 5.0g, 2.0g / 8.0g, and 0.5g / 9.5g. The compatibility test was then performed according to the following steps: visual confirmation of the liquid appearance.

[0485] step:

[0486] 1. Plug the spiral tube, shake it up and down to mix thoroughly about 10 times, and then let it stand in a constant temperature bath at 50℃ for about 10 to 15 minutes to largely eliminate air bubbles.

[0487] 2. After recording the appearance at 50°C, remove the spiral tube and allow it to return to room temperature.

[0488] 3. After recording the appearance at room temperature, for samples with uneven, cloudy appearance, let them stand overnight for further observation. For samples that are translucent to transparent and appear uniform, let them stand in a refrigerator at 5°C for 1 to 2 hours and observe the changes in appearance.

[0489] 4. After recording the appearance of the sample placed in the refrigerator at 5°C, remove the spiral tube and allow it to return to room temperature. Additionally, confirm that the appearance at room temperature is not significantly different from the appearance recorded in step 3 (room temperature).

[0490] 5. Record the appearance of the sample that turned cloudy in step 3 after standing overnight.

[0491] It should be noted that the evaluation of appearance is recorded according to the following criteria.

[0492] * Set the intermediate case between the two to "~".

[0493] ◎: Transparent and homogeneous liquid

[0494] ○: Semi-transparent to mostly transparent homogeneous liquid

[0495] Δ: Translucent homogeneous liquid

[0496] ×: Opaque, cloudy white liquid

[0497] In addition, cases where the substances are immiscible or separate overnight (due to coating) should be recorded in the table.

[0498] <Example 7: Compatibility Evaluation Test with Polyether Alcohol (C1)>

[0499] The results of evaluating the compatibility of the Ex sample with polyether alcohols (C1) having the structures and molecular weights shown in Table 9 are presented in Table 9.

[0500] [Table 9]

[0501]

[0502]

[0503] Note) Regarding the structure of C1 in Table 9, for simplicity, the EO chain and PO chain are denoted as block copolymers, but in reality they are random copolymers.

[0504] <Example 8: Compatibility Evaluation Test with Polyether Diol (C2)>

[0505] The results of the compatibility evaluation of the Ex sample and polyether diols (C2) with the structures and molecular weights shown in Table 10 are presented in Table 10.

[0506] [Table 10]

[0507]

[0508]

[0509] Note) Regarding the structure of C2 in Table 12 (Examples 8-4), for simplicity, the EO chain and PO chain are denoted as block copolymers, but in reality they are random copolymers.

[0510] <Example 9: Compatibility Evaluation Test with Polyether Triol (C3)>

[0511] The results of the compatibility evaluation of the Ex sample and polyether triol (C3) with the structure and molecular weight shown in Table 11 are presented in Table 11.

[0512] [Table 11]

[0513]

[0514] Note) The structure of C3 in Table 13 (Comparative Example 9-1) is an EO / PO random copolymer.

[0515] [About ingredient (C1)]

[0516] As shown in Table 9, when polyether alcohol is used as a diluent, in the case of the homopolymer addition polymer of PO (propylene oxide), even when the molar number of additions approaches 40 and becomes a long chain, the compatibility with component (A') is maintained, and the stability of the mixture is good. On the other hand, in the case of the addition copolymer of EO (ethylene oxide) and PO, with EO wt.% = 50 and set to a constant value, and molecular weights set to 500, 1000, and 3000, the results show that the stability deteriorates drastically when the total molar number of EO additions exceeds 30. Furthermore, the homopolymer addition polymer of EO is completely immiscible with component (A'), thus clarifying the need for PO polymerization units in the structure of polyether alcohol.

[0517] Based on these results, when polyether alcohol is used as a diluent, the upper limit of the molar addition of EO is estimated to be around 20, the upper limit of the molar addition of PO is estimated to be around 50, and the upper limit of EO wt.% in the structure is estimated to be around 60. Furthermore, according to the experience of the inventors, when the wt.% of EO in the polyether alcohol is 70 or higher, the freezing point rises, and it tends to produce precipitates or a cloudy appearance at low winter temperatures. Therefore, in this invention, the upper limit of EO wt.% when polyether alcohol is used as a diluent is set to around 60.

[0518] [About ingredient (C2)]

[0519] As shown in Table 10, when polyether glycol is used as a diluent, even when the homopolymer of PO (propylene oxide) is a long chain with an addition molar number of around 35, the compatibility with component (A') is very good, and the stability of the mixture is also good. When the addition molar number of PO is around 70, a decrease in compatibility is confirmed, but it is considered that the stability of the mixture is within acceptable limits under conditions of high component (A') concentration such as Ex / C2 = 50 / 50, and it is believed that it can also be used as a foaming agent. On the other hand, as an addition copolymer of EO (ethylene oxide) and PO, an addition copolymer with EO wt.% = 50 and a molecular weight of 1750 was tested, but it was found that the stability deteriorated drastically.

[0520] Based on these results, when polyether glycol is used as a diluent, the upper limit of the molar addition of EO is estimated to be around 10, the upper limit of the molar addition of PO is estimated to be around 70, and the upper limit of wt.% of EO in the structure is estimated to be around 30.

[0521] [About ingredient (C3)]

[0522] As shown in Table 10, polyether triols tend to have slightly lower compatibility with the compositions involved in this invention compared to polyether diols (C1) or polyether monools (C2). In the case of polyether triols as homopolymer addition polymers of PO, except for polyether triols with a Mw of 3000, a mixing ratio of Ex / C3 = 20 / 80 results in insufficient compatibility. However, under conditions of high concentrations of component (A') such as Ex / C3 = 50 / 50, the stability of the mixture is within acceptable limits, and it is considered that it can be used as a foam stabilizer. Furthermore, even under conditions of low concentrations of component (A') such as Ex / C3 = 5 / 95 (assuming the case of a premix for polyurethane foam), the stability of the mixture is within acceptable limits. On the other hand, as an addition copolymer of EO (ethylene oxide) and PO, an addition copolymer with EO wt.% = 50 and a molecular weight of 2800 was tested, but it was found that the stability deteriorated drastically.

[0523] Based on these results, when polyether triol is used as a diluent, the upper limit of EO wt.% in its structure is estimated to be around 20, and the average molecular weight range is estimated to be about 500 to 4500.

[0524] [Summarize]

[0525] Through the above examples, etc., when a specific soluble potassium salt (=component (K)) is included in a certain potassium cation concentration, and when (A') is a polyether-polysiloxane block copolymer with a specific structure and (B') is a glycol ether compound with 1 to 3 repeating olefin units of 2 to 4 carbon atoms whose terminal hydrogens are replaced by hydrocarbon groups having 1 to 8 carbon atoms and which have secondary alcoholic hydroxyl groups at other ends, a composition containing a polyether-polysiloxane block copolymer with excellent transparency and achieving a specific foam-reinforcing effect can be obtained. Similarly, practically sufficient insights have been gained regarding the appropriate combination and compatibility of the composition and component (C) involved in the present invention.

[0526] Furthermore, through the first or second manufacturing method of the present invention, a composition containing a polyether-polysiloxane block copolymer is obtained that possesses practically sufficient performance as a foam stabilizer even when using an inexpensive component (B') with a high acid value.

[0527] Based on the above experimental results, it is understood and expected that the present invention will solve the previous quality and process problems through simple means, and will enable the low-cost, stable and large-scale supply of the polyether-polysiloxane block copolymer composition, the improved manufacturing method thereof, the composition with excellent cost utilization and foam reinforcement, and the foaming agent for polyurethane foam composed therefrom.

Claims

1. A composition comprising: (A') has the general formula (1) within the molecule: [Chemical Formula 1] The structural unit represented is a polyether-polysiloxane block copolymer; In general formula (1), R independently represents a monovalent hydrocarbon group with 1 to 9 carbon atoms that does not have an aliphatic unsaturated bond, a is a number from 1 to 200, x is a number from 2 to 4, and y represents a group consisting of (C x H 2x O)y represents a polyether moiety with a molecular weight in the range of 400 to 5000, the polyether moiety contains at least one propylene oxide group, n is at least 2, and Y' represents a divalent hydrocarbon group with 2 to 8 carbon atoms bonded to adjacent silicon atoms via carbon-silicon bonds and bonded to polyoxyethylene blocks via oxygen atoms. (B') One or more glycol ether compounds, wherein the terminal hydrogen is replaced by a hydrocarbon group having 1 to 8 carbon atoms and other terminals have secondary alcoholic hydroxyl groups, the number of repeating olefinic units having 2 to 4 carbon atoms is in the range of 1 to 3, and the compounds do not contain heteroatoms other than oxygen; and (K) is selected from the potassium salts of potassium bicarbonate, potassium acetate, potassium propionate, potassium butyrate, potassium isobutyrate, and potassium 2-ethylhexanoate. The mass ratio of component (A') to component (B') is in the range of 20:80 to 60:40, and the component (A') contains potassium cations (K) from component (K) in the range of 3 to 300 wt.ppm relative to the sum of components (B'). + ).

2. The composition according to claim 1, wherein, The component (A') is a polyether-polysiloxane block copolymer in the general formula (1), where a is a number in the range of 10 to 45, y is a number that makes the molecular weight of the polyether portion represented by (CxH2xO)y in the range of 2000 to 5000, and the mass ratio of the ethylene oxide (C2H4O) units constituting the polyether portion as a whole is in the range of 35 to 90%.

3. The composition according to claim 1 or 2, wherein, Component (A') is a polyether-polysiloxane block copolymer in the general formula (1), where Y' is a divalent hydrocarbon group with 3 to 4 carbon atoms.

4. The composition according to claim 1, wherein, Component (A') has a component selected from [a specific ingredient] at the end of its molecular chain. Z 1 : Alkenyl, hydroxyl, alkoxy, or acetoxy groups that are partially bonded to the polyether; and Z 2 Monovalent hydrocarbon groups, hydroxyl groups, alkoxy groups, C1-C8 alkylene oxide groups, or hydrogen groups bonded to silicon atoms and without heteroatoms. A polyether-polysiloxane block copolymer with one or more functional groups.

5. The composition according to claim 1, wherein, Component (B') is one or more glycol ethers selected from propylene glycol monobutyl ether, dipropylene glycol monobutyl ether, tripropylene glycol monobutyl ether, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, tripropylene glycol monomethyl ether, propylene glycol monopropyl ether, dipropylene glycol monopropyl ether, tripropylene glycol monopropyl ether, propylene glycol monoethyl ether, dipropylene glycol monoethyl ether, and tripropylene glycol monoethyl ether.

6. The composition according to claim 1, wherein, The monovalent counter anion of component (K) is a counter anion with 1 to 4 carbon atoms, and contains potassium cation (K) from component (K) in the range of 3 to 100 wt.ppm relative to the sum of components (A') and (B'). + ).

7. The composition according to claim 1, wherein, The product contains, relative to the sum of component (A') and component (B'), a liquid compound (S) in the range of 20 to 15000 wt.ppm, wherein the liquid compound (S) is a solvent for component (K) and is selected from one or more of the following: (S1) water, (S2) a monovalent saturated alcohol having 1 to 4 carbon atoms, and (S3) a saturated diol compound having 3 to 9 carbon atoms.

8. The composition according to claim 1, wherein, It further contains a (C) polyether compound, said (C) polyether compound being miscible with component (A'), component (B') and component (K), and selected from components (C1) to (C3) below: (C1) Polyether alcohol represented by the following general formula (2) General formula (2): [Chemical Formula 2] In general formula (2), R represents a monovalent hydrocarbon group with 1 to 9 carbon atoms that does not have aliphatic unsaturated bonds, R'' represents methyl or ethyl, k satisfies the condition 0≤k≤20, l satisfies the condition 4≤l≤50, and the wt.% of the oxyethylene part of the polyether portion is less than 60; (C2) Polyether diols represented by the following general formula (3) General formula (3): [Chemical Formula 3] In general formula (3), R'' represents methyl or ethyl, k' satisfies the condition 0≤k'≤10, l' satisfies the condition 4≤l'≤70, and the wt.% of the ethylene oxide portion of the polyether portion is less than 30; (C3) The polyether triol is obtained by addition polymerization of 2-4 carbon alkyl esters to glycerol and / or trimethylolpropane, with the wt.% of the ethylene oxide portion of the polyether portion being less than 20 and the average molecular weight in the range of 500 to 4500.

9. A surfactant, a foam stabilizer for polyurethane foam, or a premix for polyurethane foam, comprising: The composition according to any one of claims 1 to 8.

10. A method for manufacturing the composition according to any one of claims 1 to 8, characterized in that, include: Process (I): (a1) is derived from the following general formula (4): [Chemical Formula 4] This refers to polyethers with alkenyl groups at both ends. (K) is selected from potassium salts of potassium bicarbonate, potassium acetate, potassium propionate, potassium butyrate, potassium isobutyrate, and potassium 2-ethylhexanoate. The mixing process; In general formula (4), x is a number from 2 to 4, and y represents the result of (C x H 2x O)y represents the molecular weight of the polyether moiety in the range of 400 to 5000, Y represents a monovalent hydrocarbon group with 2 to 8 carbon atoms at the end having a reactive C=C group, and the polyether moiety contains at least one propylene oxide group; Process (II): The mixture obtained in process (I) (a2) is derived from the following general formula (5): [Chemical Formula 5] This refers to organopolysiloxanes with SiH groups at both ends. (B') One or more glycol ether compounds, wherein the terminal hydrogen is replaced by a hydrocarbon group having 1 to 8 carbon atoms and secondary alcoholic hydroxyl groups at other ends, the number of repeating olefinic units having 2 to 4 carbon atoms is in the range of 1 to 3, and it does not contain heteroatoms other than oxygen, and The process of carrying out the hydrosilylation reaction is performed in the presence of an effective amount of hydrosilylation reaction catalyst; In general formula (5), R independently represents a monovalent hydrocarbon group with 1 to 9 carbon atoms that does not have aliphatic unsaturated bonds, and a represents a number from 1 to 200; Among them, relative to the sum of components (a1), (a2), and (B'), the potassium cation (K) in component (K) is contained in the range of 3 to 300 wt.ppm. + The amount of ) The sum of components (a1) and (a2): The mass ratio of component (B') is used in an amount ranging from 20:80 to 60:

40.

11. The method for manufacturing the composition according to claim 10, further comprising, in step (I), adding (S) a liquid compound and mixing component (a1), component (K) and component (S), wherein, The (S) liquid compound is a solvent for component (K) and is selected from one or more of the following: (S1) water, (S2) a monovalent saturated alcohol with 1 to 4 carbon atoms, and (S3) a saturated diol compound with 3 to 9 carbon atoms.

12. A method for manufacturing the composition according to any one of claims 1 to 8, characterized in that, include: Process (I'): (a1) is derived from the following general formula (4): [Chemical Formula 6] This refers to polyethers with alkenyl groups at both ends. (a2) is derived from the following general formula (5): [Chemical Formula 7] This refers to organopolysiloxanes with SiH groups at both ends. (B') One or more glycol ether compounds, wherein the terminal hydrogen is replaced by a hydrocarbon group having 1 to 8 carbon atoms and secondary alcoholic hydroxyl groups at other ends, the number of repeating olefinic units having 2 to 4 carbon atoms is in the range of 1 to 3, and it does not contain heteroatoms other than oxygen, and The process of carrying out the hydrosilylation reaction is performed in the presence of an effective amount of hydrosilylation reaction catalyst; In general formula (4), x is a number from 2 to 4, and y represents the result of (C x H 2x O)y represents the molecular weight of the polyether moiety in the range of 400 to 5000, Y represents a monovalent hydrocarbon group with 2 to 8 carbon atoms at the end having a reactive C=C group, and the polyether moiety contains at least one propylene oxide group; In general formula (5), R independently represents a monovalent hydrocarbon group with 1 to 9 carbon atoms that does not have aliphatic unsaturated bonds, and a represents a number from 1 to 200; Among them, the amount used is in the range of 20:80 to 60:40, where the sum of component (a1) and component (a2) is : component (B'). Process (II'): Add to the composition after the hydrogenation silanization reaction in step (I') (K) is selected from the potassium salts of potassium bicarbonate, potassium acetate, potassium propionate, potassium butyrate, potassium isobutyrate, and potassium 2-ethylhexanoate. And the process of mixing the two. Among them, relative to the sum of components (a1), (a2), and (B'), the potassium cation (K) in component (K) is contained in the range of 3 to 300 wt.ppm. + ) amount used.

13. The method for manufacturing the composition according to any one of claims 10 to 12, wherein, After step (II) or before and after step (II'), a further step of filtering the resulting composition is included.

14. A method for manufacturing the composition according to any one of claims 10 to 12, wherein, After step (II) or before and after step (II'), the process further includes adding a polyether compound (C) to the obtained composition and performing a mixing and homogenization step, wherein the polyether compound (C) is miscible with components (A'), (B') and (K) and is selected from components (C1) to (C3) below, wherein the amount of component (C) used is such that the content of component (A') in the final obtained composition is 1% by weight or more. (C1) Polyether alcohol represented by the following general formula (2) General formula (2): [Chemical Formula 8] In general formula (2), R represents a monovalent hydrocarbon group with 1 to 9 carbon atoms that does not have aliphatic unsaturated bonds, R'' represents methyl or ethyl, k satisfies the condition 0≤k≤20, l satisfies the condition 4≤l≤50, and the wt.% of the oxyethylene part of the polyether portion is less than 60; (C2) Polyether diols represented by the following general formula (3) General formula (3): [Chemical Formula 9] In general formula (3), R'' represents methyl or ethyl, k' satisfies the condition 0≤k'≤10, l' satisfies the condition 4≤l'≤70, and the wt.% of the ethylene oxide portion of the polyether portion is less than 30; (C3) The polyether triol is obtained by addition polymerization of 2-4 carbon alkyl esters to glycerol and / or trimethylolpropane, with the wt.% of the ethylene oxide portion of the polyether portion being less than 20 and the average molecular weight in the range of 500 to 4500.

15. The use of any composition according to any one of claims 1 to 8 as a surfactant, a foam stabilizer for polyurethane foam, or a premix for polyurethane foam.

16. A method for manufacturing a surfactant, a foam stabilizer for polyurethane foam, or a premix for polyurethane foam, comprising a method for manufacturing the composition according to any one of claims 10 to 14.

17. A polyurethane foam forming composition comprising the composition of any one of claims 1 to 8 or the composition obtained by the method of manufacturing the composition of any one of claims 10 to 14.

18. A polyurethane foam, which uses the composition of any one of claims 1 to 8 or the composition obtained by the manufacturing method of any one of claims 10 to 14 as raw material.

Citation Information

Patent Citations

  • JP1973075314A

  • katoseihoriesuteruretanfuoomu

    JP1976001598A

  • Monitoring system for transmission circuit

    JP1979022115A

  • Surfactant

    JP1981022395A

  • Surfactant

    JP1982014797B2